Binder component for a raw material compound for use in a molding and sintering process, particulate raw material compound, and molding and sintering process
Patent Information
- Application Number
- JP2024510258
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-08-19
- Filing Date
- 2022-08-19
- Publication Date
- 2025-01-09
- Estimated Expiration
- 2042-08-19
AI Technical Summary
Existing methods for additive manufacturing and powder injection molding face challenges in achieving high printing dimensional accuracy and efficient debinding processes, particularly in LPIM, where shape retention and strength of brown parts are insufficient due to the removal of all binder components in a single step, leading to issues like contamination, stress, distortion, and chemical reactions.
A binder component comprising a mixture of thermoplastic materials and/or wax-based materials with differing solubility, degradability, and volatility properties is used, allowing for selective debinding through solvent, thermal, or chemical processes, minimizing impact on the part and ensuring high dimensional accuracy and stability during the debinding process.
The proposed binder component enables high printing dimensional accuracy and efficient debinding with minimal shape loss or distortion, reducing contamination risks and operational complexity, while allowing for the production of complex parts with improved strength and precision.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a binder component for a raw compound for use in a molding and sintering process, a particulate raw compound comprising sinterable non-organic particles and a binder component, and a method including the steps of fusing and debinding a plurality of particulate raw compounds. [Background technology]
[0002] Methods such as additive manufacturing, powder injection molding or pressing can produce customized parts quickly and efficiently. Additive manufacturing involves adding material together (usually layer by layer), such as by fusing powder particles together. In general, a typical additive manufacturing process involves forming an initial layer of material, followed by successive additions of further layers of material, with each new layer being added onto the previously formed layer, until the entire three-dimensional structure (3D object) is materialized.
[0003] Powder injection molding involves melting and injecting material into a mold to form an object. In particular, the low pressure powder injection molding (LPIM) method requires moderate processing temperatures and pressures for these steps.
[0004] In Laser Beam Powder Bed Fusion (LB-PBF), binder-free metal powders are sintered by scanning a high-power laser beam. To eliminate the need for high-power lasers, binder-coated metal powders are formed by additive manufacturing. In a post-processing step, the binder is removed and the metal powder is sintered.
[0005] All these new methods require well-defined raw compound containing a sinterable material and a binder. Recently, a variety of such raw compound has been described in the literature. US Pat. No. 5,399,433 describes a powder for use in selective laser sintering processes that contains a (metal) substrate coated with a polymeric binder. The binder comprises, for example, an amorphous copolymer of butyl methacrylate and styrene or of methyl methacrylate and butyl methacrylate. Optionally, the binder may further comprise a plasticizer, which will not be described in detail.
[0006] Patent document 2 describes an element consisting of powder particles containing metal particles such as Fe, Co, Ni, W, Mo or metal carbides, which are bonded via a polyamide and a plasticizer / wax mixture, which is not described in detail.
[0007] Patent Document 3 describes a low pressure powder injection molding machine, kit and method. Low pressure powder injection molding (LPIM) is a variation of the traditional high pressure powder injection molding (HPIM) process, and recent advances in feedstock formulation have created new opportunities to cost-effectively manufacture more complex shapes in both high and low volume production. Typically, a pneumatic molding machine is used to fill the powder and binder mixture into the mold cavity.
[0008] Recently, Tafti et al. described the effect of thermal debinding conditions on the sintered density of low-pressure powder injection molded iron parts (see Non-Patent Document 1). A low-viscosity feedstock was injected into a rectangular mold cavity, thermally debound at three different debinding temperatures, and sintered. Increasing the debinding temperature from 600 to 850 °C reduced the number of fines, resulting in an increase in (sintered) density from (6.2 to 5.1 g / cm). 3 The pore diameter decreased (from 9 to 14 μm), which resulted in an increase in the average pore size (from 9 to 14 μm), and the pore circularity also decreased (from 67 to 59%).
[0009] According to Tafti et al. (see above), in the conventional HPIM process, the binder, which consists of a blend of low and high molecular weight polymers (also called the first and second binders, respectively), is removed in two stages. In the first stage, depending on the binder system and the powder properties, the first binder is extracted either by a solvent, a supercritical fluid such as supercritical carbon dioxide, or a catalyst such as concentrated nitric acid. In the second stage, the second binder, which acts as a skeleton to hold the shape, is removed during the final burnout cycle before the sintering process.
[0010] Typically, LPIM uses a multi-component binder that does not include a high melting point backbone polymer, and can include, for example, a wax-based carrier, a surfactant, and a thickener.
[0011] However, in the absence of a skeletal binder, one of the main challenges encountered with the LPIM process is the lack of shape retention and strength of the brown part, since all binder components are removed in a single step during debinding (e.g., during thermal wick debinding), which relies on capillary extraction of the liquid binder to extract it from the green part. This approach consists of embedding the injected part in a wicking powder bed (e.g., graphite, alumina, or other inert powders) and heating it up to a pre-sintering temperature (e.g., the softening temperature of the binder) in a protective atmosphere, if necessary. The powder bed acts as a wicking medium that draws the molten binder out of the heated part by capillary flow. As a physical support, it maintains the fragile debound part until the pre-sintering of the powder particles. Thermal wick debinding requires careful selection of key parameters such as pore size of the wicking medium, debinding temperature, heating rate, protective atmosphere or pre-sintering temperature to ensure adequate binder extraction while avoiding drawbacks such as undesirable stresses, distortions, defects, chemical reactions, etc. However, the use of fine powders can result in contamination of the green parts, which may require further cleaning.
[0012] For example, Patent Document 4 discloses a composite material containing tungsten and bronze. To form a homogeneous mixture, tungsten and bronze powders (non-organic particles) are mixed with an organic binder. The organic binder is usually a thermoplastic binder, a wax or a wax mixture. A preferred binder includes a low molecular weight wax or wax mixture that melts at a temperature preferably between room temperature and about 120°C, more preferably between about 50°C and 90°C, and even more preferably between about 55°C and 65°C. For example, the wax may be paraffin wax, microcrystalline wax, polybutene wax, polyethylene wax, carnauba wax, etc., or a mixture of two or more thereof. The thermal debinding process includes heating the molded part in a furnace to a temperature at which the binder is rapidly converted by pyrolysis into gaseous products that are extruded by a flowing protective atmosphere. As the part is heated, the binder melts. A wicking powder, for example a powder containing alumina, can be used to create a capillary force gradient that draws the binder out of the part.
[0013] Patent Document 5 describes fine fibers (filaments) containing a metal and / or ceramic powder, a thermoplastic binder containing a thermoplastic polymer and at least one plasticizer, and optionally additives. Suitable thermoplastic polymers described therein are, for example, polyurethanes, polyamides, polyvinylpyrrolidones, polyacrylates, or polyolefins, and suitable plasticizers are selected from aromatic or heteroaromatic carboxylic acid esters, such as hydroxybenzoic acid esters.
[0014] Patent Document 5 discloses a fine fiber (filament) suitable for use in a 3D printing device, which comprises or consists of a metal powder and / or ceramic powder, a thermoplastic binder comprising a thermoplastic polymer and at least one plasticizer, and optionally additives. It also discloses a method for producing a molded body comprising the fine fiber. The molded body is obtained by printing a molded green body with the fine fiber, removing at least a portion of the plasticizer, and sintering.
[0015] Recently, a method for additively manufacturing metal and / or glass and / or ceramic parts has been described. Patent document 6 discloses a method for additively manufacturing metal and / or glass and / or ceramic parts. Raw compound particles are prepared from substrate particles and at least a two-phase binder. The raw compound particles are selectively melted in layers by electromagnetic radiation and a molded part is additively manufactured. The molded part is recovered from the unmolten mixture and the at least two-phase binder is subsequently removed continuously. Finally, the debound molded part is sintered.
[0016] However, various factors during the printing process can compromise the dimensional accuracy of the part compared to the target data that defines it. For example, it is often difficult to produce parts with sharp, precise edges and low porosity (green), and improvements in the molding process must not come at a disadvantage or degradation during the debinding process. [Prior art documents] [Patent documents]
[0017] [Patent Document 1] WO 95 / 30503 [Patent Document 2] DE 19648926 C1 [Patent Document 3] US 20190134712 A1 [Patent Document 4] US 2003 / 0161751 A1 [Patent Document 5] WO 2016 / 004985 A1 [Patent Document 6] WO 2018 / 197082 [Non-patent literature]
[0018] [Non-Patent Document 1] Tafti et al., Metals 2021,11,264-276 Summary of the Invention
[0019] It is therefore an object of the present invention to provide a binder component for a raw compound that enables high printing dimensional accuracy and a simple and economical method for debinding in a method using a raw compound containing the binder component.
[0020] The present invention relates to a binder component for a raw compound for use in a molding and sintering process, Based on the total volume of the binder component (b), bi) 3 to 70% by volume of at least one first thermoplastic material and / or wax-based material; b-ii) 30 to 97% by volume of at least one second thermoplastic material and / or wax-based material, or a plasticized thermoplastic material and / or a wax-based material; Includes; The first thermoplastic material and / or wax-based material and the second thermoplastic material and / or wax-based material differ in at least one property selected from the following: (1) Solubility in solvents (2) decomposition induced by heat and / or reactants; and (3) Volatility; the first thermoplastic material and / or wax-based material is less soluble, less degradable, or less volatile than the second thermoplastic material and / or wax-based material; T crossis T P It is higher than the range of 60K (T P is the DSC melting peak temperature of the binder component (b), and T cross is the temperature at the intersection of the storage modulus G' curve and the loss modulus G'' curve in the dynamic viscoelastic measurement of the binder component (b).
[0021] Hereinafter, the expression "(plasticized) thermoplastic material and / or wax-based material" is intended to encompass both "thermoplastic material and / or wax-based material" and "plasticized thermoplastic material and / or wax-based material".
[0022] The present invention also relates to a particulate raw material compound for use in a compacting and sintering process, comprising: a) Sinterable non-organic particles dispersed throughout the particulate raw compound (sinterable non-organic particles are particles having a maximum particle size A of at least 80% of the particles in the range of 100 nm to 200 μm). max having a particle size distribution ... b) The binder component (b).
[0023] The present invention also relates to a method including the steps of fusing a plurality of particulate raw material compounds and debinding the same.
[0024] The following description of the preferred embodiments refers to binder components, particulate feedstock compounds, and methods unless otherwise noted.
[0025] Generally, the forming process of an additive manufacturing process involves providing a powder bed of a particulate raw material compound in a build space that is typically heated to an elevated temperature, e.g., 50-60°C. The particulate raw material compound in the powder bed can absorb energy from an energy beam from a radiation source, e.g., a laser beam, resulting in an increase in temperature in localized regions of the powder material. The localized temperature increase can selectively densify or melt the particulate raw material compound and bond the particulate raw material compound to each other in a predetermined manner.
[0026] It has been found that the melting behavior of the binder strongly influences the printing accuracy. In localized areas, it is desirable to form strong bonds between the particulate raw compound, but the formation of bonds to neighboring or adjacent particles should be avoided. Raw compounds with non-optimized binder content can dissipate heat to adjacent particles, which can soften and adhere to the outer surface of the part, resulting in a poor surface definition.
[0027] In powder injection molding, the particulate feedstock is melted by a heated barrel and / or screw and injected into a mold by a plunger or by pressure or gravity. Similarly, melt behavior has been found to have a strong influence on the processing parameters in powder injection molding. The low viscosity of the feedstock compound allows for smaller injection molding machine sizes and overall mold sizes, both of which are significantly smaller than those required for HPIM. The lower costs associated with smaller mold sizes provide the opportunity to produce complex parts in a cost-effective manner, whether in low or high production volumes. Additionally, the ease of molding and high flowability of the feedstock compound allows for larger parts to be produced than in HPIM.
[0028] The binder components of the present invention have a very limited temperature transition from solid or semi-solid to fluid, which reduces the impact on adjacent feed compound particles in 3D printing. As a result, the feed compound particles exposed to the energy beam are transformed from solid to fluid at a relatively low temperature, allowing for the formation of dense green parts without affecting the adjacent feed compound. This very limited temperature transition from solid or semi-solid to fluid is called T, as described in more detail below. P and T cross This is reflected by the small difference between
[0029] Typically, Differential Scanning Calorimetry (DSC) can measure the physical properties of materials, such as the glass transition temperature, melting temperature, enthalpy of fusion, and the like.
[0030] The melting step results in an endothermic peak in the DSC curve, and the melting temperature is the melting peak temperature T P Refers to...
[0031] A DSC curve may contain a single melting peak. Alternatively, a DSC curve may contain several melting peaks, i.e. several local maxima. For the purposes herein, the melting peak temperature T P is defined as the temperature of the global maximum. The binder component (b) preferably exhibits a single melting peak.
[0032] In one embodiment, the binder component (b) has a melting peak temperature T of less than 180° C., preferably from 10° C. to 180° C., more preferably from 20° C. to 160° C., most preferably from 30° C. to 140° C., particularly from 35° C. to 120° C., particularly from 40° C. to 100° C., particularly from 45° C. to 90° C., particularly from 50° C. to 85° C. P The melting peak temperature T P allows for selective densification or melting with as little additional energy (e.g., laser energy) as possible, and allows for the convenient use of low-energy laser sources.
[0033] In this specification, T P is determined in accordance with DIN EN ISO 11357-3 with a second heating after the first heating / cooling cycle. For this purpose, the sample is heated with a first heating gradient from -20°C to a temperature 20K higher than the completion of all thermal events, then cooled to -20°C and finally heated again with a second heating gradient from -20°C to a temperature 20K higher than the completion of all thermal events. The respective heating and cooling rates are 10K / min. By "thermal event" for the purposes herein is meant a thermal event other than decomposition, in other words an essentially reversible thermal event.
[0034] Typically, dynamic viscoelastic measurements can determine the dynamic viscoelastic properties of a material, including its storage modulus G' and loss modulus G''.
[0035] The storage modulus G' represents the elastic modulus of a material. It is proportional to the rate at which deformation energy can be stored in the material and recovered from it after stress removal.
[0036] The loss modulus G'' describes the viscous part of a material. It corresponds to the proportion of energy lost through internal friction that is converted into heat.
[0037] T cross is the temperature at which the storage modulus G' curve and the loss modulus G'' curve intersect in the dynamic viscoelastic measurement of the binder component. This temperature is also referred to in the literature as the "crossover" temperature, and refers to the state of the material where the transition from the molten state to the viscous state of the material occurs. If the G' and G'' curves cross multiple times, T cross is the intersection point at the maximum temperature. The expression "maximum temperature" is understood by those skilled in the art to refer to the maximum temperature below which decomposition occurs.
[0038] A sample of the binder component (b) is subjected to dynamic viscoelasticity measurement.
[0039] In principle, T cross can be determined during the heating or cooling process. Kinetic effects such as supercooling or interrupted thermal transitions can be cross To eliminate the influence of kinetic effects, the T cross It may be desirable to measure T during heating. cross and T measured during cooling cross If different, T cross Use the higher value.
[0040] Due to possible non-equilibrium transitions during the measurement of the binder, the measurement of the raw compound may give more accurate results in individual cases. It is believed that kinetic effects are less likely to occur when the raw compound is subjected to the measurement, since the non-organic particles (a) may act as crystallization nuclei and reduce the diffusion process.
[0041] For example, the storage modulus G curve and the loss modulus G'' curve are P The dynamic viscoelastic properties are recorded by measuring the dynamic viscoelasticity while heating the material from a temperature 20 K lower than the melting point (temperature above the melting point) to the temperature at which the material is completely melted.
[0042] The cooling and heating rates were each 1 K / min, first cooling from 110°C to 60°C and then heating to 110°C.
[0043] In the context of this patent application, dynamic viscoelastic measurements for determining the storage and loss moduli are carried out in accordance with DIN 53019-4:2016-10. The measurements are suitably carried out in oscillatory mode at a frequency of 1 Hz using a plate-plate geometry with a diameter of 40 mm. The measurement gap can be 0.15 mm.
[0044] To carry out the measurement, the temperature at which a sample of binder component (b) is completely liquefied, i.e. the estimated T cross The geometry is heated to a temperature of about 20 K above the T of the binder component (b) and the sample is placed on the hot lower plate. The cooling and heating rates are each 1 K / min. cross The mixture is cooled from a temperature of about 20 K above the first nodal point temperature to a temperature about 10 K below the first nodal point temperature, and then heated to a temperature of about 20 K above the melting temperature of the binder component (b).
[0045] During the cooling ramp, the measurement starts in deformation-controlled mode with a constant deformation γ = 0.1%. After the trigger point is reached, the measurement is switched to the shear stress-controlled mode with a constant shear stress (σ = 100 Pa for the binder and σ = 700 Pa for the raw compound).
[0046] For the heating ramp, the measurement starts in shear stress control mode with a constant shear stress σ = 300 Pa. After the trigger point is reached, the measurement is switched to deformation control mode with a constant deformation γ = 0.1%. The trigger point is located at the transition between the solid and liquid states. Between both states the shear modulus changes significantly, which requires different control modes depending on the measurement needs.
[0047] During the heating or cooling ramp, the sample undergoes a phase transformation, so a change of measurement mode is necessary to stay in the linear viscoelastic range. For example, during a cooling ramp, the sample changes from a liquid to a rigid state. The deformation in the liquid state must not be too large, otherwise the sample is no longer in the linear viscoelastic range. If a liquid is subjected to a certain deformation, the liquid will assume a completely new shape or position when the applied force or stress is released. The sample reaches the selected deformation in the liquid state, so the measurement at this stage is deformation controlled. In the rigid state, no deformation is achieved and the torque of the rheometer is reached. Therefore, the measurement mode must be switched to a shear stress control mode. The switch of the measurement from the deformation control mode to the shear stress control mode is set by a trigger point. The trigger point is located at the transition between the solid and liquid states. Between both states, the shear modulus changes significantly, so different control modes are required depending on the measurement needs. The trigger point can be any specific point or criterion that allows a change of measurement mode in the linear viscoelastic range. The same is true for the heating ramp.
[0048] According to the present invention, the binder component is T P Compared to T cross is high within a range not exceeding 60K, preferably not exceeding 50K, more preferably not exceeding 45K, most preferably not exceeding 40K, and particularly not exceeding 35K. This satisfies the condition that T cross T P This also includes situations where the
[0049] In one embodiment, the binder component (b) is init and [T P +25K] is at least 94%, preferably at least 95%, more preferably at least 96%, most preferably at least 97%, particularly at least 98%, and especially at least 99%. initis the initial melting temperature. The term "total enthalpy of melting" refers to the sum of the endothermic DSC peaks that lie in the range of 10 °C to 20 K above the completion of all thermal events, for example in the range of 10 °C to 200 °C. The enthalpy of melting is usually reported as J / g and can be derived from the area enclosed by the endothermic DSC peak curve and the baseline.
[0050] For evaluation, the portion of the curve after complete melting was rotated horizontally. A baseline was drawn horizontally from the end of the thermogram. The initial melting temperature (T init ) is T P Melting temperature T is the first intersection point between the baseline and the thermogram at a temperature below 100° C. and indicates the initial melting temperature of binder component (b). P is the temperature at the maximum height of the peak.
[0051] Either a sample of binder component (b) without sinterable non-organic particles (a) or a sample of the raw compound, binder component (b) with sinterable non-organic particles (a), is subjected to DSC. The overall shape of the DSC curve and the melting peak temperature are essentially unchanged, since the sinterable non-organic particles (a) do not exhibit a phase transition in the temperature range of the DSC measurement. The measurement of a sample containing binder component (b) and sinterable non-organic particles (a) will result in a different absolute peak area compared to the measurement of a sample containing only binder component (b). This is due to the "dilution" of the sample by the sinterable non-organic particles (a). However, since the ratios are expressed as percentages, the results are essentially unchanged.
[0052] According to the invention, the first thermoplastic and / or wax-based material (bi) and the second thermoplastic and / or wax-based material (b-ii) differ in at least one property selected from the following: (1) Solubility in a solvent, preferably selected from alcohols such as ethanol or propanol; aromatic compounds such as benzene, toluene or xylene; esters such as ethyl acetate; ethers such as diethyl ether or tetrahydrofuran; ketones such as acetone; alkanes such as hexane or heptane; halogenated hydrocarbons such as n-propyl bromide, trichloroethylene, perchloroethylene, n-methylpyrrolidine; and mixtures thereof, water, and gases in a supercritical state; and (2) decomposability induced by heat and / or a reactant, preferably nitric acid; (3) Volatility, for example due to evaporation induced by temperature and / or reduced pressure. It should be noted that the first thermoplastic material and / or the wax-based material (bi) is less soluble, less degradable or less volatile than the second thermoplastic material and / or the wax-based material (b-ii).
[0053] The binder component (b) comprises 3 to 70 vol. %, preferably 5 to 60 vol. %, more preferably 7 to 50 vol. %, most preferably 10 to 40 vol. %, in particular 12 to 35 vol. %, in particular 15 to 30 vol. % of the first thermoplastic material and / or wax-based material (bi), based on the total volume of the binder component (b).
[0054] The binder component (b) further comprises 30 to 97% by volume, preferably 40 to 95% by volume, more preferably 50 to 93% by volume, most preferably 60 to 90% by volume, in particular 65 to 88% by volume, in particular 70 to 85% by volume of a second (plasticized) thermoplastic and / or wax-based material (b-ii), based on the total volume of the binder component (b).
[0055] Different solubility or decomposition properties or different volatility allow selective debinding. In a selective debinding process, one binder component (in the context of the present patent application, the second thermoplastic material and / or the wax-based material (b-ii)) is removed while another binder component (the first thermoplastic material and / or the wax-based material (bi)) remains in the part to be produced, holding the sinterable non-organic particles together. Such debinding processes, e.g. solvent debinding, thermal debinding, chemical debinding, etc., are known per se.
[0056] The present invention uses partial debinding, such as thermal, solvent, or chemical debinding, thereby avoiding the disadvantages associated with methods that rely on a wicking step.
[0057] In embodiments particularly suitable for small parts, thermal debinding alone can be performed without the need for a wicking step. In such a wicking step, the entire amount of binder softens in a narrow temperature range, and so the part needs to be supported with a wicking powder to prevent shape loss or distortion. This makes the process time-consuming and limits the design freedom of the part. The use of even finer powders may contaminate the green part, requiring further cleaning. The method according to the invention comprises gradually removing the second thermoplastic and / or wax-based material (b-ii) from the part by decomposition and / or evaporation, with minimal impact on the first thermoplastic and / or wax-based material (bi).
[0058] In one embodiment, the drawbacks associated with processes that rely solely on thermal debinding are also avoided, especially for large parts. During thermal debinding of the second thermoplastic material and / or wax-based material, as the temperature increases, an increasing amount of binder evaporates from the entire binder mass. If the binder portion evaporates too quickly without a reliable exit path, the part may break and lose its integrity. Therefore, to prevent the part from bursting, the binder evaporation rate must be extremely slow and the degradation rate must be kept low. This makes thermal debinding of the second thermoplastic material and / or wax-based material a difficult and time-consuming process, especially for large parts. The method according to the invention involves gradually removing the second thermoplastic material and / or wax-based material from the outside towards the center of the part in a manner that has minimal impact on the first thermoplastic material and / or wax-based material (i.e., by solvent debinding and chemical debinding).
[0059] Suitably, in a solvent debinding step, one binder component can be selectively removed from the green part by means of dissolving said binder component in a solvent, while the second binder component remains within the green part. Therefore, the binder components should have different solubilities in the solvent, e.g., different molecular weights or polarities.
[0060] Any given polymer or wax may be highly soluble in one solvent, e.g., a non-polar solvent, but poorly soluble or insoluble in another, e.g., a more polar solvent. Thus, whether a particular polymer or wax qualifies as a (bi) or (b-ii) material depends on the solvent used in the debinding step. When changing solvents, e.g., from a polar solvent to a less polar or non-polar solvent, or vice versa, the classification of the binder component as (bi) or (b-ii) may be reversed.
[0061] For example, when solvent debinding is performed using acetone as the solvent, the material remaining in the debound part (first thermoplastic material and / or wax-based material (bi)) may be a polymer or wax that is poorly soluble or insoluble in acetone, while the binder component that is removed (second thermoplastic material and / or wax-based material (b-ii)) may be a polymer or wax that is soluble in acetone.
[0062] In one embodiment, the solubility of the first thermoplastic material and / or wax-based material (bi) is less than 0.1 g, preferably less than 0.05 g, more preferably less than 0.01 g, most preferably less than 0.005 g, in 100 g of solvent, and in particular insoluble in the solvent. The solubility of the second thermoplastic material and / or wax-based material (b-ii) is in the range of 0.1 g to 500 g, preferably 0.5 g to 300 g, more preferably 1 g to 200 g, most preferably 2 g to 175 g, particularly 3 g to 150 g, and particularly 5 g to 100 g, in 100 g of solvent at a predetermined temperature. The predetermined temperature is 10° C. to [T P -5°K], preferably in the range of 20°C to 80°C, more preferably 30°C to 70°C, most preferably 35°C to 65°C, and particularly preferably 40°C to 60°C.
[0063] A chemical debinding (also called "catalytic debinding") process is described, for example, in DE 102005027216 A1. For this purpose, the molded part to be debound is placed in a debinding oven, in which it is heated to a suitable processing temperature. Process gases containing reactants (such as nitric acid) are then introduced into the oven. By contacting the binder-containing molded part with the hot reactants, the binder components can be burned off from the molded part. Depending on their chemical stability towards the reactants, one or more binder components may remain in the molded part.
[0064] In one embodiment, the first thermoplastic material and / or the wax-based material (bi) are semi-crystalline. The term "semi-crystalline" characterizes a polymer that has a high degree of intermolecular and intramolecular order. The semi-crystalline nature of a polymer is characterized by a first order transition or crystalline melting point (T m ) can be confirmed.
[0065] Preferably, the first thermoplastic material and / or the wax-based material (bi) are semi-crystalline as they exhibit a distinct transition separating the fluid and solidified states, and furthermore, they are characterized by increased strength due to crystallization upon solidification.
[0066] The first thermoplastic and / or wax-based material (bi) and the second thermoplastic and / or wax-based material (b-ii) may be selected from a variety of materials.
[0067] Suitable polymers include: Polyolefins; e.g. Polyethylenes such as Lupolen 2420, Lupolen 5261 Z (available from LyondellBasell Industries Holdings BV), Sabic P6006NA (available from Sabic), BorPure® MB5569, BorPure® MB6561, BorPure® MB7541 (available from Borealis), Exceed® 1018, Enable® 2203MC (available from Exxon Mobile);
[0068] Polypropylenes such as BC250MO, BC545MO (available from Borealis), Adstif HA5029, Adstif HA600U, Adstif EA600P, Adstif EA648P, Clyrell RC213M, Clyrell RC5056, Hostalen PP H5416 (available from LyondellBasell Industries Holdings BV), Achieve® Advanced PP6936G2, Achieve® Advanced PP6945G1, Achieve® Advanced PP6035G1, ExxonMobil® PP1105E1, ExxonMobil® PP3155E5, ExxonMobil® PP9574E6 (available from Exxon Mobile);
[0069] Polyolefin copolymers of monomers such as ethene, propene, butene, hexene, preferably propylene-ethylene copolymers such as Vistamaxx 8880 (available from Exxon Mobile);
[0070] Polyolefin copolymers with non-olefin monomers such as ethylene-n-butyl acrylate copolymers such as EnBA EN 33091 (available from Exxon Mobile) or ethylene vinyl acetate copolymers such as Escorene® UltraUL 8705 (available from Exxon Mobile), ELVAX® 250 (available from Dow);
[0071] Modified polyolefins such as grafted polypropylene Licocene® PP MA 1332 (available from Clariant);
[0072] Poly(meth)acrylates such as polymethyl methacrylate (PMMA);
[0073] polyamides such as polyamide 12; copolyamides, for example Griltex 2439 A, Griltex 1796 A, Griltex 1500 A, Griltex D 2638A (available from EMS-CHEMIE HOLDING AG); Orgasol 3502 D (available from Arkema AG), UNI-REZ 2620, UNI-REZ 2638, UNI-REZ 2656, UNI-REZ 2674, UNI-REZ 2720, UNI-REZ 2291 (available from Kraton Corporation); polycarbonates, poly-α-methylstyrene, polyurethanes; water-soluble or water-dispersible thermoplastic polymers such as polyalkylene glycols, polyvinyl alcohols, polyvinyl lactams, polyvinylpyrrolidones, and copolymers thereof;
[0074] Polyesters such as polycaprolactone, polylactide, polyglycolide, poly(hydroxyalkanoates) such as poly(3-hydroxybutyrate), poly(3-hydroxyvalerate), poly(hydroxybutyrate-co-hydroxyvalerate) ENMAT Y1000P (available from TianAn Biologic Materials Co., Ltd.), phthalates such as polyethylene terephthalate (PET), polytrimethylene terephthalate (PTT), polybutylene terephthalate (PBT), polycarbonates, copolyesters such as Griltex 6E, Griltex 8E, Griltex 9E, Griltex D 1365E, Griltex D 1442E, Griltex D 1539E, Griltex D 1655E, Griltex D 1841E, Griltex D 1682E, Griltex D 1939E, Griltex D 2132E, Griltex D 2245E;
[0075] polyethers such as polyetheretherketone or polyoxymethylene; and mixtures thereof.
[0076] It is understood that it is also possible to combine polymers from different classes.
[0077] Typically, polyamides can be produced by the reaction of carboxylic acids with amines to amides or by the reaction of carboxylic acids with moieties / derivatives of amines. Polyamide homopolymers can be produced by the reaction of one monomer, i.e., an amino acid or lactam having 4-25 carbon atoms, such as polyamide 6 by ring-opening polymerization of ε-caprolactam. Polyamides can be produced by the polycondensation reaction of a diamine having 4-25 carbon atoms with a dicarboxylic acid having 4-25 carbon atoms or its salt. For example, polyamide 6.6 by the polycondensation reaction of hexamethylenediamine with adipic acid or the reaction of hexamethylenediamine adipate. Copolyamides can be produced by the polycondensation reaction of various amines with various carboxylic acids, preferably diamines having 4-25 carbon atoms such as hexamethylenediamine, dicarboxylic acids having 4-25 carbon atoms such as adipic acid, azelaic acid, dodecanedioic acid, aminocarboxylic acids having 4-25 carbon atoms such as aminoundecanoic acid, or their salts. By mixing and reacting various monomers into ternary, quaternary and multi-component copolyamides, the properties of the copolyamides, such as the melting point and / or viscosity and / or adhesion, can be adjusted. For example, by mixing the monomers PA6 (ε-caprolactam), PA6.6 (hexamethylenediamine with adipic acid or hexamethylenediamine adipate) and PA12 (aminolauric acid) in a ternary system, a melting point of 110-120°C can be obtained for a mixture of 20-40% PA6.6, 20-40% PA6 and 30-50% PA12. On the other hand, the melting points of pure PA6.6, PA6 and PA12 are 250°C, 215°C and 176°C, respectively. The reaction with branched and / or aromatic carboxylic acids and / or branched and / or aromatic amines, as well as with further reaction partners, such as ethers, esters, elastomers and many others, is known per se.
[0078] Griltex 2439 A (available from EMS-CHEMIE HOLDING AG) is particularly preferred.
[0079] Polyolefins are a group of thermoplastic polymers formed by the polymerization of olefins such as propylene, ethylene, isoprene, and butene, which are commonly obtained from natural carbon sources such as crude oil and gas. Polyolefins contain only carbon and hydrogen atoms bonded together, with or without side branches. The properties of polyolefins depend mainly on the type of monomer and the polymerization route, resulting in various molar masses and crystallinity. They can be easily modified by introducing various functional groups or mixed with other polymers and fillers to obtain properties tailored to the required application. Polyolefins such as low density polyethylene (LDPE), linear low density polyethylene (LLDPE), high density polyethylene (HDPE), medium density polyethylene (MDPE), metallocene polyethylene (mPE); crosslinked polyethylene (xPE); cyclic polyolefins (COC); syndiotactic, isotactic, and atactic polypropylene (sPP, iPP, aPP); random and homopolypropylene (rPP, hPP); thermoelastic polyolefins (TPO), as well as other special types of polyolefins such as polybutene (PB), polymethylpentene (P4MP), (EP), ethylene vinyl acetate (EVA), and mixtures (blends) and copolymers thereof, can be used. Polyolefins are usually characterized by high chemical resistance (not affected by alkalis and dilute acids) and low solvent solubility (not affected by most solvents at temperatures below 60°C).
[0080] Vistamaxx 8880, Achieve™ Advanced PP6936G2 (available from Exxon Mobile) are particularly preferred.
[0081] Water-soluble or water-dispersible thermoplastic polymers such as polyalkylene glycols or polyvinyl polymers selected from polyvinyl alcohol, polyvinyl lactams and copolymers contain functional groups that make the polymer soluble or dispersible in common solvents such as acetone, ethanol and water. Among the polyalkylene glycols, polyethylene glycols are preferred, such as polyethylene glycol 200 to polyethylene glycol 20.000 (available from Carl Roth GmbH+Co.KG). Polyvinyl alcohols can usually be produced by saponification of polyvinyl acetate. The properties of polyvinyl alcohol, such as its solubility in water, are affected by the degree of saponification. Among the polyvinyl lactams, polyvinyl pyrrolidone is particularly preferred. Copolymers of polyvinyl pyrrolidone and polyvinyl alcohol can also be used.
[0082] Polyesters are usually polymers obtained by condensation reactions of difunctional reactants such as diols and diacids, and are characterized by the presence of ester functions (-COO-) along the chain. Linear polyesters can be divided into three classes: aliphatic, partially aromatic, and aromatic. Aliphatic polyesters are obtained from aliphatic dicarboxylic acids (or esters) and aliphatic diols. Partially aromatic polyesters are obtained from aromatic dicarboxylic acids (or esters) and aliphatic diols. Aromatic polyesters have all the ester functions attached to aromatic rings. By using different difunctional reactants, copolyesters can be obtained. Branched polyesters can be obtained by using at least partially polyfunctional, i.e. more than difunctional, reactants.
[0083] Polyethers are typically polymers with ether linkages in the "backbone" of the polymer chain.
[0084] It is understood that the classes of polymers described also include derivatives of thermoplastic elastomers. Thermoplastic elastomers are so-called multiblock copolymers composed of short crystallizable hard segments and long flexible segments. Due to their chemical structure, thermoplastic elastomers exhibit a unique combination of thermoplastic and elastomeric behavior, which can be beneficial. Thermoplastic elastomers based on polystyrene, polyolefins, polyvinyls, polyurethanes, polyesters and polyamides are known per se.
[0085] The term "wax" is a generic technical term for a group of organic substances that can generally be described in terms of their physical and technical properties. In particular, waxes are characterized by being solids with a melting point above 40°C (usually between 50°C and 160°C) and a low melt viscosity (less than 10 Pa·s at 10°C above the melting point). Waxes melt without decomposing. Waxes can also be classified into natural waxes of fossil origin, such as paraffin, montan wax, etc.; natural waxes of natural origin, such as beeswax, carnauba wax, etc.; semi-synthetic waxes (also called chemically modified natural waxes), such as ethylene-bis-stearamide; and synthetic waxes, such as polyolefin waxes. In the context of this patent application, the expression "wax-based material" is intended to include not only waxes, but also wax-based substances such as ester waxes, higher alcohols or polyhydric alcohols, higher fatty acids exhibiting wax-like properties, and mixtures thereof.
[0086] Suitable wax-based materials include: Paraffin waxes, such as microcrystalline wax; Ester waxes such as beeswax, candelilla wax, and carnauba wax;
[0087] esters of organic acids such as sulfonic or carboxylic acids, preferably esters of fatty acids having 6 to 40 carbon atoms, or esters of aromatic carboxylic acids such as benzoic acid, phthalic acid, or hydroxybenzoic acid;
[0088] Amide waxes, for example amides of organic acids such as sulfonic or carboxylic acids, preferably amides of fatty acids having 6 to 40 carbon atoms, for example oleamides such as Deurex A27P (available from Deurex AG), erucamides such as Deurex A26P (available from Deurex AG), ethylene-bis-stearamides such as Deurex A20K (available from Deurex AG); sulfonamides such as N-ethyltoluene-4-sulfonamide;
[0089] Polyolefin waxes, for example polyethylene waxes, for example Deurex E06K, Deurex E08, Deurex E09K, Deurex E10K (available from Deurex AG), VISCOWAX® 111, VISCOWAX® 116, VISCOWAX® 123, VISCOWAX® 135 (available from Innospec Leuna); Oxidized polyethylene waxes, such as Deurex EO40K, Deurex EO42, Deurex EO44P, Deurex E76K (available from Deurex AG), VISCOWAX® 252, VISCOWAX® 262, VISCOWAX® 271, VISCOWAX® 2628 (available from Innospec Leuna); Polyolefin copolymer waxes, preferably ethylene vinyl acetate, e.g., VISCOWAX® 334, VISCOWAX® 453 (available from Innospec Leuna); Polypropylene waxes such as Deurex P36K, Deurex P37K (available from Deurex AG); Oxidized polypropylene wax;
[0090] Fischer-Tropsch waxes, such as VESTOWAX EH100, VESTOWAX H2050 MG, VESTOWAX SH105, Shell GTL Sarawax SX105, Shell GTL Sarawax SX80 (available from Evonik Industries AG);
[0091] Higher organic acids such as fatty acids having 10 to 40 carbon atoms; higher or polyhydric alcohols, such as alcohols having 10 to 40 carbon atoms; Polyethylene glycol; and mixtures thereof.
[0092] In one embodiment, the wax-based material is a mixture of different wax-based materials.
[0093] In one embodiment, the binder component b-ii) is a plasticized thermoplastic and / or wax-based material. By "plasticized thermoplastic and / or wax-based material" is meant a combination of a thermoplastic and / or wax-based material and a plasticizer. Generally, a plasticizer is a high-boiling liquid, usually with a boiling point above 180° C., which is compatible with the thermoplastic and / or wax-based material to reduce its melt viscosity. Those skilled in the art will understand that the ternary combination of a first thermoplastic and / or wax-based material, a second thermoplastic and / or wax-based material, and a plasticizer forms a homogeneous phase. Usually, a plasticizer is a polar compound, meaning that its chemical structure contains at least one highly electronegative heteroatom, such as an oxygen atom or a nitrogen atom.
[0094] Suitably, the plasticized thermoplastic and / or wax-based material b-ii) comprises a plasticizer in an amount of at most 50 vol.-%, preferably at most 40 vol.-%, more preferably at most 30 vol.-%, most preferably at most 20 vol.-%, in particular at most 15 vol.-%, in particular at most 10 vol.-%, based on the total amount of b-ii).
[0095] Suitable plasticizers include: liquid aliphatic carboxylic acid esters, such as dimethyl sebacate, di-n-octyl sebacate, dimethyl succinate, dimethyl adipate, dibutyl adipate, dioctyl adipate, dimethyl azelate, dioctyl azelate, di-n-butyl maleate, dioctyl maleate, butyl oleate, dimethyl hexanedioate, benzyl laurate, methyl laurate, ethyl myristate, diacetyl triethyl citrate, acetyl tributyl citrate; Liquid aromatic carboxylic acid esters, such as dimethyl phthalate, methyl 2-hydroxybenzoate, butyl 4-hydroxybenzoate, butyl benzoate, 2-ethylhexyl benzoate, bis(2-ethylhexyl) terephthalate; Alkyl sulfonic acid phenyl esters; Liquid amides, such as n-butylbenzenesulfonamide, N-ethyltoluene-2-sulfonamide, N-ethyl-4-toluenesulfonamide; Liquid organic acids, for example carboxylic acids such as fatty acids such as caprylic acid, myristoleic acid, etc.; higher alcohols such as 1-decanol, 2-decanol, and 1-octadecanol; Polyhydric alcohols such as butanediol, ethylene glycol, and propylene glycol; and mixtures thereof.
[0096] Paraffin waxes, such as microcrystalline waxes, are usually derived from petroleum, for example, they are obtained as refined mixtures of solids containing primarily saturated aliphatic hydrocarbons produced by the de-oiling of certain fractions resulting from the petroleum refining process.
[0097] Typically, the ester wax may be a naturally occurring wax or a synthetically produced wax. Preferably, the naturally occurring ester wax is selected from beeswax, candelilla wax, and carnauba wax. The synthetically produced ester wax is preferably selected from esters of carboxylic acids, preferably esters of fatty acids having 5 to 34 carbon atoms, more preferably esters of fatty acids having 10 to 28 carbon atoms, or esters of hydroxybenzoic acid. Preferably, the ester wax comprises an ester of hydroxybenzoic acid, such as an ester of 4-hydroxybenzoic acid. Loxiol 2472 (4-hydroxybenzoic acid behenyl ester, available from Emery Oleochemicals GmbH) is particularly preferred.
[0098] Typically, polyolefin waxes can be produced by pyrolysis of branched high molecular weight polyolefins or by direct polymerization of olefins. Suitable polyolefin waxes include, for example, homopolymers of propylene or higher 1-olefins, copolymers of propylene and ethylene or higher 1-olefins, or copolymers thereof with each other. The higher 1-olefins are preferably linear or branched olefins having 4 to 20, more preferably 4 to 6, carbon atoms. These olefins may have aromatic substituents conjugated to the olefinic double bonds. For example, 1-butene, 1-hexene, 1-octene or 1-octadecene, styrene, etc. The polyolefin waxes may be oxidized. Particularly preferred are polyethylene waxes such as Deurex E06K (available from Deurex AG).
[0099] Typically, amide waxes, such as amides of sulfonic or carboxylic acids, preferably fatty acids, can be prepared by condensation reaction of an amide, such as ethylenediamine, with a sulfonic or carboxylic acid, preferably a fatty acid, having 5 to 34 carbon atoms, preferably 10 to 28 carbon atoms. Particularly preferred are oleamides, such as Deurex A27P (available from Deurex AG), erucamides, such as Deurex A26P (available from Deurex AG), and ethylene-bis-stearamides, such as Deurex A20K (available from Deurex AG).
[0100] According to the invention, the first thermoplastic and / or wax-based material (bi) and the second thermoplastic and / or wax-based material (b-ii) differ in at least one property selected from solubility in a solvent, decomposition induced by heat and / or reactants, and volatility. If the binder components (bi) and (b-ii) have different solubilities in a solvent, and the first thermoplastic and / or wax-based material (bi) is less soluble than the second thermoplastic and / or wax-based material (b-ii), debinding is performed as a solvent debinding step using a suitable solvent. In other words, during solvent debinding, at least a part of the second thermoplastic and / or wax-based material (b-ii) dissolves in a suitable solvent, while the majority of the first thermoplastic and / or wax-based material (bi) remains in the green part. Thus, the first thermoplastic and / or wax-based material (bi) provides the necessary shape retention of the debound part, and therefore the first thermoplastic and / or wax-based material (bi) is also referred to hereinafter as "skeleton polymer".
[0101] Preferably, the first thermoplastic material and / or the wax-based material (bi) is a backbone polymer selected from polyolefins, polyolefin waxes, polyamides, poly(meth)acrylates, polyesters, polyethers, and mixtures thereof. Suitable polyolefins include polyethylene, polypropylene, polyolefin copolymers with different monomers, polyolefin copolymers with non-olefin monomers (such as ethylene vinyl acetate or ethylene n-butyl acrylate copolymers), modified polyolefins, polyolefin waxes, and mixtures thereof. Representative examples of suitable polymers that are commercially available are those mentioned above.
[0102] In one embodiment, the backbone polymer has a DSC melting peak temperature T P : less than 160°C, preferably less than 150°C, more preferably less than 140°C, most preferably less than 130°C, particularly less than 120°C, particularly less than 110°C, particularly less than 100°C, especially less than 90°C.
[0103] Preferably, the backbone polymer has a melt viscosity according to ISO 1133 at 160°C using 2.16 kg: less than 1500 Pa·s, preferably less than 1300 Pa·s, more preferably less than 1000 Pa·s, most preferably less than 800 Pa·s, particularly less than 600 Pa·s, particularly less than 500 Pa·s, particularly less than 400 Pa·s, particularly less than 300 Pa·s, particularly less than 200 Pa·s, especially less than 100 Pa·s.
[0104] Preferably, the backbone polymer has a melt viscosity according to ISO 1133 at 190°C using 2.16 kg: less than 1500 Pa·s, preferably less than 1300 Pa·s, more preferably less than 1000 Pa·s, most preferably less than 800 Pa·s, particularly less than 600 Pa·s, particularly less than 500 Pa·s, particularly less than 400 Pa·s, particularly less than 300 Pa·s, particularly less than 200 Pa·s, especially less than 100 Pa·s.
[0105] Preferably, the backbone polymer has a melt volume flow rate of at least 5 cm using 2.16 kg at 160° C. according to ISO 1133. 3 / 10 min, preferably at least 10 cm 3 / 10 min, more preferably at least 20 cm 3 / 10 min, most preferably at least 30 cm 3 / 10 minutes, especially at least 40 cm 3 / 10 minutes, especially at least 50 cm 3 / 10 minutes, especially at least 60cm 3 / 10 minutes, especially at least 70cm 3 / 10 minutes, especially at least 80cm 3 / 10 minutes, especially at least 90cm 3 / 10 minutes, especially at least 100 cm 3 / 10 minutes, especially at least 110cm 3 / 10 minutes, especially at least 120cm 3 / 10 minutes, especially at least 130cm 3 / 10 minutes, especially at least 140cm 3 / 10 minutes, especially at least 150 cm 3 / 10 minutes, especially at least 160cm 3 / 10 minutes, especially at least 170cm 3 / 10 minutes, especially at least 180cm 3 / 10 minutes, especially at least 190cm 3 / 10 minutes, especially at least 200 cm 3 / 10 min.
[0106] Preferably, the backbone polymer has a melt volume flow rate of at least 5 cm using 2.16 kg at 190° C. according to ISO 1133. 3 / 10 min, preferably at least 10 cm 3 / 10 min, more preferably at least 20 cm 3 / 10 min, most preferably at least 30 cm 3 / 10 minutes, especially at least 40 cm 3 / 10 minutes, especially at least 50 cm 3 / 10 minutes, especially at least 60cm 3 / 10 minutes, especially at least 70cm3 / 10 minutes, especially at least 80cm 3 / 10 minutes, especially at least 90cm 3 / 10 minutes, especially at least 100 cm 3 / 10 minutes, especially at least 110cm 3 / 10 minutes, especially at least 120cm 3 / 10 minutes, especially at least 130cm 3 / 10 minutes, especially at least 140cm 3 / 10 minutes, especially at least 150 cm 3 / 10 minutes, especially at least 160cm 3 / 10 minutes, especially at least 170cm 3 / 10 minutes, especially at least 180cm 3 / 10 minutes, especially at least 190cm 3 / 10 minutes, especially at least 200 cm 3 / 10 min.
[0107] Preferably, b-ii) is selected from polar waxes, or plasticized thermoplastic materials and / or wax-based materials comprising polar plasticizers.
[0108] As used herein, the term "polar wax" refers to a wax whose chemical structure consists essentially of or is composed of carbon and hydrogen atoms and which contains at least one highly electronegative heteroatom, such as an oxygen, nitrogen, or sulfur atom.
[0109] Preferably, the polar wax is selected from polyolefin waxes, ester-based waxes, amide waxes, higher organic acids, higher or polyhydric alcohols, polyethylene glycols, and mixtures thereof.
[0110] Preferably, the ester waxes include esters of organic acids. Preferably, the amide waxes include amides of organic acids such as sulfonic acids or carboxylic acids. Representative examples of suitable waxes that are commercially available are listed above.
[0111] Preferably, the polar wax has a dropping point according to DIN ISO 2176 in the range from 20 to 160°C, more preferably in the range from 30 to 150°C, even more preferably in the range from 35 to 140°C, particularly preferably in the range from 40 to 130°C, particularly preferably in the range from 40 to 120°C, particularly preferably in the range from 40 to 110°C, particularly preferably in the range from 40 to 100°C and most preferably in the range from 40 to 90°C.
[0112] More preferably, the polar waxes have a melt viscosity according to DIN EN ISO 3104 at 160°C of less than 30 Pa·s, preferably less than 20 Pa·s, more preferably less than 10 Pa·s, most preferably less than 5 Pa·s, particularly less than 3 Pa·s, especially less than 1 Pa·s, particularly less than 700 mPa·s, particularly less than 300 Pa·s, especially less than 100 mPa·s, especially less than 50 mPa·s.
[0113] More preferably, the polar waxes have a melt viscosity according to DIN EN ISO 3104 at 120°C of less than 40 Pa·s, preferably less than 30 Pa·s, more preferably less than 20 Pa·s, most preferably less than 10 Pa·s, in particular less than 5 Pa·s, in particular less than 3 Pa·s, in particular less than 1 Pa·s, in particular less than 700 mPa·s, in particular less than 300 Pa·s, in particular less than 100 mPa·s.
[0114] In a further preferred embodiment, b-ii) is a wax-based material selected from aromatic esters and aromatic sulfonamides, or a plasticized thermoplastic material and / or a wax-based material comprising a plasticizer selected from aromatic esters and aromatic sulfonamides. The alcohol of the aromatic ester may be an alcohol having 1 to 40 carbon atoms. The aromatic sulfonamide may have at least one organic moiety having 1 to 40 carbon atoms at the amide nitrogen atom.
[0115] Particularly preferred combinations of bi) and b-ii) that have proven useful are:
[0116] In one embodiment, (bi) is a polyamide, preferably a copolyamide, and (b-ii) is a wax-based material selected from esters of organic acids and / or amides of organic acids, preferably aromatic esters and aromatic sulfonamides, or a plasticized thermoplastic material and / or a wax-based material comprising a plasticizer selected from aromatic esters and aromatic sulfonamides. The polyamide preferably has a DSC melting peak temperature T P , satisfying constraints on melt viscosity and melt volumetric flow rate.
[0117] In one embodiment, (bi) is a polyester, preferably a polycaprolactone, or a copolyester, preferably a poly(hydroxybutyrate-co-hydroxyvalerate), and / or a polyester-based thermoplastic elastomer, and (b-ii) is an ester wax, an ester of an organic acid, an amide wax, a higher organic acid, and / or a higher or polyhydric alcohol. The polyester or copolyester preferably has a DSC melting peak temperature T as defined above for the "backbone polymer". P , satisfying constraints on melt viscosity and melt volumetric flow rate.
[0118] In one embodiment, (bi) is a polyolefin such as polyethylene; polypropylene; polyolefin copolymers of monomers such as ethene, propene, butene, hexane; polyolefin copolymers with non-olefin monomers such as ethylene n-butyl acrylate copolymer and / or ethylene vinyl acetate copolymer; and / or polyolefin wax; and / or modified polyolefin. Also, (b-ii) is an ester wax, an ester of an organic acid, an amide wax, a higher organic acid, and / or a higher or polyhydric alcohol. The polyolefin preferably has a DSC melting peak temperature T as defined above for the "backbone polymer". P , satisfying constraints on melt viscosity and melt volumetric flow rate.
[0119] In one embodiment, the first thermoplastic and / or wax-based material (bi) is a polyethylene wax and the second thermoplastic and / or wax-based material (b-ii) is an amide wax. The combination of polyethylene wax and amide wax is suitable for solvent debinding using ethanol or acetone as the solvent.
[0120] In a preferred embodiment, the first thermoplastic and / or wax-based material (bi) is a polyamide and the second thermoplastic and / or wax-based material (b-ii) is a wax, preferably an ester-based wax. The combination of polyamide and wax is suitable for solvent debinding using acetone as the solvent.
[0121] In a preferred embodiment, the first thermoplastic and / or wax-based material (bi) is a polypropylene wax and the second thermoplastic and / or wax-based material (b-ii) is an amide wax. The combination of polypropylene wax and amide wax is suitable for solvent debinding using ethanol as the solvent.
[0122] In a preferred embodiment, the first thermoplastic and / or wax-based material (bi) is a polyethylene wax and the second thermoplastic and / or wax-based material (bii) is a water-soluble or water-dispersible thermoplastic polymer such as polyethylene glycol. The combination of polyethylene wax and water-soluble or water-dispersible thermoplastic polymer is suitable for solvent debinding using water or an aqueous solution as the solvent.
[0123] The following table shows combinations of (bi), (b-ii) and solvents that have proven useful in the practice of the present invention, although many other combinations are possible and are not intended to be limiting.
[0124] [Table 1]
[0125] [Table 2]
[0126] [Table 3]
[0127] [Table 4]
[0128] The first thermoplastic and / or wax-based material (bi) and the second thermoplastic and / or wax-based material (b-ii), respectively, may consist of a single material or a mixture of materials meeting the requirement of at least one property difference defined above.
[0129] The binder component (b) may contain a dispersant. For example, one of the materials constituting the second thermoplastic material and / or the wax-based material (b-ii) may act as a dispersant. Otherwise, an external dispersant may be further incorporated.
[0130] Typically, the dispersing agent acts as an adhesion promoter and / or compatibilizer between the binder components (bi) and / or (b-ii); and / or between the non-organic particles (a) and the binder component (b).
[0131] Suitably, the dispersing agent is selected from fatty acids having 10 to 24 carbon atoms, such as capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, behenic acid, lignoceric acid, or oleic acid, preferably stearic acid.
[0132] Preferably, the external dispersing agent is selected from metal salts of fatty acids. Typically, the metal can be selected from alkali metals, alkaline earth metals, or transition metals such as lithium, sodium, potassium, magnesium, calcium, strontium, barium, and zinc. Preferably, the fatty acid can be selected from fatty acids having 5 to 34 carbon atoms, preferably 10 to 28 carbon atoms, as described above. Preferred metal salts of fatty acids are selected from sodium stearate, magnesium stearate, zinc stearate, or magnesium oleate.
[0133] Since the viscosity of the binder component (b) is within the above range, in a molten state, the binder component (b) is uniformly and homogeneously dispersed among the sinterable non-organic particles (a) and bonds with each of the sinterable non-organic particles (a) or each of the particulate raw material compounds.
[0134] It may be desirable to incorporate a viscosity reducing or thickening agent to adjust the viscosity of the binder component (b). The thickening agent serves to increase the viscosity of the binder component when melted. This increased viscosity prevents sagging of the non-organic sinterable particles, facilitates uniform flow of the particles, and provides resistance to segregation and settling.
[0135] In particular the viscosity of the binder component (b) is adjusted (i.e. lowered or increased) by a thickening or thinning agent. A thinning agent is used to lower the viscosity of the overall binder component. A thickening agent is used to increase the viscosity of the overall binder component. A thinning agent can act as a plasticizer allowing control of the rheological properties and flow properties of the first thermoplastic and / or wax-based material (bi) or the second thermoplastic and / or wax-based material (b-ii).
[0136] Preferably, the thickening or reducing agent is selected from waxes and / or thermoplastic polymers, such as polyolefins and polyolefin waxes, polyamide and amide waxes, paraffin waxes, ester waxes; vinyl esters such as ethylene vinyl acetate; abietates; adipates; alkylsulfonates; amines and amides such as formamides, hydroxyl alkyl formamides, amines, diamines; azelates; benzoates; citrates; chlorinated paraffins; ether-ester plasticizers; glutarates; hydrocarbon oils; isobutyrates; maleates; oleates; phosphates; phthalates; sulfonamides; oily liquids such as peanut oil, fish oil, castor oil; and mixtures thereof. Preferably, polyethylene wax Deurex E09K, having a viscosity of <40 mPa·s at 140° C., can be used as a reducing agent, and Deurex E25, having a viscosity of 4000 mPa·s at 140° C., or polyolefin-based compounds of even higher molecular weight can be used as thickening agents.
[0137] In one embodiment, the thickening or thinning agent and / or dispersing agent may be present in an amount of 0 to 15 vol.%, preferably 0.01 to 10 vol.%, more preferably 0.02 to 8 vol.%, and most preferably 0.5 to 6 vol.%, based on the total volume of binder component (b).
[0138] In one embodiment, the binder component (b) is heated to a temperature of 130° C.; and -1 The viscosity, measured at a shear rate of 1000 rpm, is less than 6 Pa·s, preferably less than 5 Pa·s, more preferably less than 4 Pa·s, most preferably less than 3 Pa·s, in particular less than 2 Pa·s, especially less than 1 Pa·s, in particular less than 700 mPa·s, in particular less than 400 mPa·s, in particular less than 200 mPa·s. The viscosity is measured according to EN ISO 3219:1994.
[0139] In one embodiment, the binder component (b) is heated to a temperature of 110° C.; and -1The viscosity, measured at a shear rate of 10 Pa·s, preferably less than 8 Pa·s, preferably less than 6 Pa·s, more preferably less than 5 Pa·s, most preferably less than 4 Pa·s, in particular less than 3 Pa·s, in particular less than 2 Pa·s, in particular less than 1 Pa·s, in particular less than 600 mPa·s, in particular less than 300 mPa·s. The measurement of the viscosity is carried out in accordance with EN ISO 3219:1994.
[0140] In one embodiment, the binder component (b) is subjected to a temperature of 100° C.; and -1 The viscosity, measured at a shear rate of less than 10 Pa·s, preferably less than 8 Pa·s, more preferably less than 6 Pa·s, most preferably less than 5 Pa·s, in particular less than 4 Pa·s, particularly less than 3 Pa·s, in particular less than 2 Pa·s, in particular less than 1 Pa·s, in particular less than 500 mPa·s. The viscosity measurement is carried out in accordance with EN ISO 3219:1994.
[0141] Granular raw material compound
[0142] As used herein, the term "particulate" means that the raw compound is composed of particles of any shape, including irregular, cylindrical, spheroidal, or roughly spherical, or fine fibers.
[0143] The particulate raw material compound of the present invention comprises sinterable non-organic particles (a) and a binder component (b) as described above, and is useful in compacting and sintering processes.
[0144] The present invention therefore further relates to a particulate raw material compound for use in a compacting and sintering process, comprising: a) Sinterable non-organic particles dispersed throughout the particulate raw compound (sinterable non-organic particles are particles having a maximum particle size A of at least 80% of the particles in the range of 100 nm to 400 μm). max having a particle size distribution ... b) The binder components described above.
[0145] The sinterable non-organic particles (a) include any sinterable material known in the art. Typically, the sinterable non-organic particles (a) are selected from metals, alloys, glass particles and ceramic particles.
[0146] In one embodiment, the metal is selected from iron, stainless steel, steel, copper, bronze, aluminum, tungsten, molybdenum, silver, gold, platinum, titanium, nickel, cobalt, chromium, zinc, niobium, tantalum, yttrium, silicon, magnesium, calcium, and combinations thereof. Suitably, the metal particles have a maximum particle size A in the range of 500 nm to 400 μm, preferably 1 μm to 150 μm, more preferably 3 μm to 50 μm, and most preferably 5 μm to 25 μm, of at least 85%, preferably at least 90%, more preferably at least 95%, and most preferably at least 99% of the particles. max The particle size distribution has
[0147] Suitably, the alloy is selected from stainless steels (316L, 17-4 PH), steels such as chromium-nickel steels, bronzes, copper alloys such as Hovadur, nickel-based alloys such as Hastelloy or Inconel, cobalt-chromium alloys such as cobalt and Stellite, aluminium alloys such as aluminium 6061, tungsten heavy alloys, titanium alloys such as grades 1 through 5 (Ti-6Al-4V) up to grade 38 according to ASTM.
[0148] In one embodiment, the ceramic particles are selected from oxides such as aluminum oxide, silicon oxide, zirconium oxide, titanium oxide, magnesium oxide, yttrium oxide, carbides such as silicon carbide, tungsten carbide, nitrides such as boron nitride, silicon nitride, aluminum nitride, silicates such as steatite, cordierite, mullite, and combinations thereof. Suitably, the ceramic particles have a maximum particle size A of at least 85%, preferably at least 90%, more preferably at least 95%, and most preferably at least 99% of the particles in the range of 200 nm to 25 μm, preferably 300 nm to 10 μm, more preferably 400 nm to 7 μm, and most preferably 500 nm to 3 μm.max The particle size distribution has
[0149] In one embodiment, the glass particles are selected from non-oxide glasses, such as halide glasses, chalcogenide glasses, oxide glasses, such as phosphate glasses, borate glasses, silicate glasses, e.g., aluminosilicate glasses, lead silicate glasses, boron silicate glasses, soda-lime silicate glasses, quartz glasses, alkali silicate glasses, and combinations thereof. Suitably, the glass particles have a maximum particle size A of at least 85%, preferably at least 90%, more preferably at least 95%, and most preferably at least 99% of the particles in the range of 200 nm to 25 μm, preferably 300 nm to 10 μm, more preferably 400 nm to 7 μm, and most preferably 500 nm to 3 μm. max The particle size distribution has
[0150] Suitably, the sinterable non-organic particles (a) may comprise a combination of more than one of the above-mentioned metals, alloys, glass particles and ceramic particles, such as hard metals or metal matrix composites (also called metal ceramic composites).
[0151] In one embodiment, the particulate raw material compound has a volumetric content of sinterable non-organic particles (a) of about 0.70 to 0.99·φ r , preferably about 0.75 to 0.98·φ r , more preferably about 0.80 to 0.96·φ r , and most preferably about 0.82 to 0.95·φ r , especially about 0.84 to 0.94·φ r , especially about 0.86 to 0.93·φ r Contains an amount of φ r is the critical solids loading by volume. The remainder is made up of binder component b).
[0152] The term "critical solids loading" usually refers to the volumetric amount of sinterable non-organic particles in a raw compound at a critical limit. The "critical limit" is reached when the addition of sinterable non-organic particles to the raw compound causes the raw compound to become hard and no longer flowable due to the infinity of relative viscosity. Physically, the "critical solids loading" defines the maximum loading of particles while still retaining a continuous material, and is the limit beyond which it is no longer possible to continue loading solid powders into the binder matrix. In this context, the term "relative viscosity" refers to the viscosity of the raw compound relative to the viscosity of the pure binder, isolating the effect of the sinterable non-organic particles. The viscosity of the raw compound increases with the addition of sinterable non-organic particles.
[0153] There are several ways to determine the critical solids loading. For example, the peak of the torque of the kneader can be determined as more and more metal powder is added to the binder. Usually, after the critical solids loading is reached, the torque decreases again as the raw compound becomes brittle. Alternatively, pycnometer measurements can be used: up to the critical solids loading, the theoretical density coincides with the density measured with the pycnometer, but above the critical solids loading, the measured density is below the theoretical density due to porosity (see also 1990, RM German, Powder Injection Molding, Metal Powder Industries Federation 1990, p. 129-130). Rheological measurements can be used to determine φ·η r :( r It is also possible to estimate the value of the critical solids loading by plotting φ (-1) versus η (JSChong, EB Christiansen, AD Baer, J. Appl. Polym. Sci. 1971, 15, 2007-2021). In this context, φ denotes the loading and η r indicates relative viscosity.
[0154] Alternatively, in one embodiment, the particulate raw material compound comprises sinterable non-organic particles (a) in an amount of about 20-90 volume %, preferably 30-80 volume %, more preferably 40-75 volume %, most preferably 45-70 volume %, and especially 50-65 volume %, and a binder component (b) in an amount of about 10-80 volume %, preferably 20-70 volume %, more preferably 25-60 volume %, most preferably 30-55 volume %, and especially 35-50 volume %.
[0155] The binder component (b) comprises at least two binder components: a first thermoplastic and / or wax-based material (bi) and a second thermoplastic and / or wax-based material (b-ii). Optionally, the binder component (b) may comprise further functional additives in view of good processability.
[0156] Each particulate raw compound comprises a plurality of sinterable non-organic particles (a) dispersed throughout the particulate raw compound within a matrix of binder component (b) and held together by binder component (b). The presence of a plurality of sinterable non-organic particles (a) per particulate raw compound allows the shape of the particulate raw compound to be independent of the shape of the sinterable non-organic particles (a). Thus, for example, a particulate raw compound having a substantially spherical shape can be produced without the sinterable non-organic particles (a) having to be spherical. This reduces production costs because sinterable non-organic particles (a) having arbitrary or irregular particle shapes or a broader particle size distribution are more readily available than powders having a specific, e.g., spherical, particle shape.
[0157] In one embodiment, the particulate raw material compound is mixed at a temperature of 130° C. and a shear rate of 1 s -1 The viscosity, measured at 100° C., is less than 600 Pa·s, preferably less than 400 Pa·s, more preferably less than 350 Pa·s, most preferably less than 250 Pa·s, in particular less than 150 Pa·s, in particular less than 50 Pa·s, in particular less than 10 Pa·s. The viscosity is measured according to EN ISO 3219:1994.
[0158] In one embodiment, the particulate raw material compound is mixed at a temperature of 110° C. and a shear rate of 1 s -1 The viscosity, measured at 100° C., is less than 800 Pa·s, preferably less than 550 Pa·s, more preferably less than 450 Pa·s, most preferably less than 350 Pa·s, in particular less than 200 Pa·s, in particular less than 100 Pa·s, in particular less than 60 Pa·s. The viscosity is measured according to EN ISO 3219:1994.
[0159] In one embodiment, the particulate raw material compound is mixed at a temperature of 100° C. and a shear rate of 1 s -1 The viscosity, measured at 1000 Pa·s, preferably less than 850 Pa·s, more preferably less than 700 Pa·s, most preferably less than 550 Pa·s, in particular less than 400 Pa·s, in particular less than 250 Pa·s, in particular less than 100 Pa·s, is measured according to EN ISO 3219:1994.
[0160] The particulate raw material compound is produced, for example, by subjecting a suspension of sinterable non-organic particles (a) and a solvent (e.g., an alcohol solvent in which binder component (b) is dissolved) to spray drying. Alternatively, a solidified melt of binder component (b) in which sinterable non-organic particles (a) are dispersed may be pulverized. Alternatively, larger particulate raw material compounds may be blended in an extruder and then granulated.
[0161] Typically, for use in 3D printing and pressing, the particulate raw material compound has a maximum particle size B in the range of 0.005 to 0.3 mm, preferably 0.008 to 0.2 mm, more preferably 0.01 to 0.2 mm, and most preferably 0.015 to 0.15 mm, of which at least 80% by volume, preferably at least 90% by volume, more preferably at least 95% by volume, and most preferably at least 99% by volume. max The particle size distribution has
[0162] When used in an injection molding process, the particulate raw compound has a maximum particle size B in the range of 1 to 10 mm, preferably 2 to 8 mm, and more preferably 3 to 5 mm. max has.
[0163] method
[0164] The present invention further relates to a method comprising the steps of: - fusing a plurality of particulate raw material compounds to obtain a green part; and - partially debinding the green part by selectively removing the second thermoplastic material and / or wax-based material (b-ii) to obtain a brown part comprising sinterable non-organic powder particles (a) bound to one another by the first thermoplastic material and / or wax-based material (bi).
[0165] In one embodiment, the method is selected from additive manufacturing methods such as laser additive manufacturing or extrusion additive manufacturing; injection molding methods such as medium pressure injection molding or low pressure injection molding; pressing methods, and casting methods, preferably additive manufacturing methods such as laser additive manufacturing or extrusion additive manufacturing.
[0166] In the context of this patent application, the term "fusing" refers to "selectively melting and solidifying" if the method is selected from additive manufacturing methods using radiation; or the term "fusing" refers to "melting and solidifying" if the method is selected from injection molding, casting, microfiber printing, or pellet printing; or the term "fusing" refers to "compressing" or "compressing, partially or completely melting and solidifying" if the method is selected from pressing methods.
[0167] Careful selection of ingredients and process parameters favorably results in parts that are free of cracks, which may occur, for example, if the debinding operation is performed too quickly or under harsh conditions. Therefore, ingredients and process parameters are preferably selected such that harmful conditions are avoided.
[0168] Typically, in additive manufacturing processes using radiation from a laser array, radiative heating elements, such as laser additive manufacturing or HP's Multi Jet Fusion process, the particulate raw compound is applied in layers and then densified and solidified, for example by cooling. During densification, the binder component (b) contained in the particulate raw compound is selectively melted in layers by electromagnetic radiation, for example from a laser.
[0169] In a preferred embodiment, the step of fusing the plurality of particulate feedstock compounds comprises the steps of: - providing a first layer of raw compound particles; - selectively densifying the first layer of raw compound particles to bond the compound particles together in a predetermined manner to produce a first layer of molded part; - providing at least one additional layer of raw compound particles on the first layer of molded part; and - selectively densifying additional layers of the raw compound particles and bonding the raw compound particles to one another in a predetermined manner to produce at least one additional molded part layer, the first molded part layer and the additional molded part layer forming a green part.
[0170] Typically, extrusion additive manufacturing is a method in which a raw compound is fed as fine fibers or granules, melted by a heated printer extruder head, and deposited in layers to create a green part. The print head is moved under computer control to determine the print geometry. Typically, the head moves in two dimensions, depositing one horizontal plane or layer at a time. The workpiece or print head is then moved vertically a small distance to start a new layer. After the printing process, the shaped raw compound can be removed as a solidified green part. Green parts contain sinterable non-organic powder particles and a binder.
[0171] Injection molding, typically medium pressure injection molding or low pressure injection molding, involves mixing finely powdered raw materials with a binder to produce a raw compound, which is then melted and injected (molded) in a liquid state into a mold. After cooling, the shaped raw compound solidifies in the mold and can be removed to obtain a green part. The green part includes the raw materials and the binder. If the fine powder material is a metal or alloy, the process is called a metal injection molding (MIM) process. If the fine powder material is a ceramic, the process is called a ceramic injection molding (CIM) process. Typically, processes involving fine powder materials are called powder injection molding (PIM) processes. Further suitable sinterable non-organic powder particles include, for example, glass, ceramic, or polymer, or mixtures thereof.
[0172] Generally, the casting process involves melting the feed compound and pouring it into a mold in a liquid state (molding). After cooling, the molded feed compound solidifies in the mold and is removed to obtain the green part. The green part includes the feed compound and the binder. In one embodiment, the mold is a lost casting mold. That is, the mold can be used for only one green part, for example because it must be destroyed to obtain the green part. Lost casting molds can be produced by various methods such as casting or additive manufacturing, for example extrusion additive manufacturing or inkjet additive manufacturing. The lost form can be printed with a polymer that is also soluble in a solvent, for example acrylonitrile-butadiene-styrene (ABS) in acetone. In one embodiment, a portion of the mold is printed and the portion is at least partially filled with the feed compound. These steps are repeated until the printing of the mold and the filling of the mold are completed. Preferably, both the mold and the green part can be dissolved in the same solvent and de-bindered. The green part contains sinterable non-organic powder particles and a binder. After the casting forming process, the green part undergoes a conditioning operation to densify (sinter) the powder.
[0173] Typically, in a pressing process, a green part can be formed from a particulate raw material compound that includes finely powdered raw materials and a binder by applying high pressure to the particulate raw material compound to densify (press molding). Preferably, the densification can involve heat, and the particulate raw material compound may be partially or completely melted. The green part includes sinterable non-organic powder particles and a binder. After the pressing molding process, the green part is subjected to a conditioning operation to densify (sinter) the powder.
[0174] The aforementioned steps can also be combined. In the following, preferred step combinations are described in detail. These steps can be carried out using a particulate raw material compound as described above. Alternatively, any other particulate raw material compound comprising an organic binder component and sinterable non-organic particles can be employed. In particular, a binder component can be employed comprising a first thermoplastic material and / or a wax-based material and a second thermoplastic material and / or a wax-based material, the first thermoplastic material and / or the wax-based material differing from the second thermoplastic material and / or the wax-based material in at least one property as described above.
[0175] In one embodiment, a green part is cast or molded and then printed via an extrusion-based process.
[0176] In one embodiment, the green parts are manufactured through various processes (e.g., one part is 3D printed and another part is molded) and are taken out and bonded as green or brown parts. A suitable method for bonding is selected from welding and gluing methods. A suitable adhesive for bonding is selected from a slurry containing a polymeric binder such as polyvinyl alcohol, galantine or agar, a solvent such as water or alcohol, and suitable non-organic particles, preferably sinterable non-organic particles, more preferably sinterable non-organic particles of the same composition as the sinterable non-organic particles of the green or brown parts.
[0177] In one embodiment, the method comprises the steps of: (i) providing a first green part by additive manufacturing; - placing the first green part into a mold; - melting a portion of the particulate raw material compound according to the invention and casting or injection molding the molten portion in a mold, the molten portion forming the interface of the first green part; - solidifying the first green part so that it becomes an integral part of the cast green part; - Partial debinding of the cast green parts to obtain brown parts.
[0178] Preferably, the first green part is manufactured by a 3D printing method, which allows the first green part to shrink uniformly and not warp during the sintering process. Therefore, the first green part is preferably manufactured by selectively melting and solidifying a plurality of particulate raw material compounds according to the present invention by additive manufacturing to obtain the first green part.
[0179] In other words, a first green part is produced by 3D printing, and the 3D printed first green part is then placed into a mold and overmolded and / or overcast.
[0180] Such a process combination is advantageous in terms of process efficiency when only one or more main parts of the manufactured part have a complex design and / or require high geometric accuracy, while the remaining parts of the part (e.g., around the main parts) require relatively lower geometric accuracy. Also possible is the combination of various materials, such as in a two-component metal injection molding process. In other words, a first green part is manufactured in one material, and then the 3D printed first green part is placed in a mold and overmolded and / or overcast with another suitable material.
[0181] In this case, a first green part is produced from a first portion of the raw compound by 3D printing and placed in a mold, after which a second portion of the raw compound is melted and cast or injected into the mold.
[0182] The raw compound of the invention is particularly suitable for carrying out such a combination of steps due to the high dimensional stability of the first green part and the high compatibility of the molten second part of the raw compound, i.e. the high ability of the molten second part to adhere to the first green part.
[0183] The mold is configured to receive the molten second portion of the feedstock compound such that the molten second portion forms an interface with the first green part. In other words, the molten second portion contacts the first green part for bonding and becomes an integral part of the cast green part after solidification. For example, the molten second portion is deposited adjacent to the first green part or deposited adjacent to and on the first green part.
[0184] Preferably, the mold and / or the first green part has a DSC melting peak temperature T P The first green part is preheated to a temperature close to 1000° C. This is to promote better bonding between the first green part and the second part cast of the base compound.
[0185] In one embodiment, the method comprises the steps of: - providing a first green part; - placing a first green part into a build chamber; - providing a first layer of raw compound particles on a first green part; - selectively densifying the first layer of raw compound particles to bond the compound particles together in a predetermined manner to produce a first molded part layer bonded to the first green part; - optionally providing at least one additional layer of raw compound particles on the first layer of molded part; and - selectively densifying the additional layers of raw compound particles and bonding the raw compound particles to one another in a predetermined manner to produce at least one additional molded part layer bonded to the first molded part layer, and the first molded part layer and the additional molded part layer integral with the first green part to form an integral part; - Partial debinding of the integral part to obtain the brown part.
[0186] In this case, a first green part is produced from a first portion of the raw compound by a molding, casting or additive manufacturing process and placed in a build chamber. A second portion of the raw compound is then applied and a portion of the particulate raw compound is melted using radiation from a laser array, a radiative heating element, or the like. For example, in laser additive manufacturing or HP's multi-jet fusion process, the particulate raw compound is applied in layers and then densified and solidified, for example by cooling. During densification, the binder component (b) contained in the particulate raw compound is selectively melted in layers by electromagnetic radiation, for example from a laser.
[0187] Such a process combination is advantageous in terms of process efficiency when only one or more main parts of the manufactured part have a complex design and / or require high geometrical accuracy, while the remaining parts of the part (e.g. the periphery of the main parts) require relatively lower geometrical accuracy. Also possible is the combination of various materials, such as in two-component metal injection molding. In other words, the first green part is manufactured of one material and the applied particulate feed compound is another suitable material.
[0188] The raw material mixture of the present invention is particularly suitable for carrying out such a combining step due to the high dimensional stability of the first green part and the high compatibility of the molten second part of the raw compound, i.e. the high ability of the molten second part to adhere to the first green part.
[0189] The build chamber is configured to receive a particulate feed compound over the first green part. When selectively densified, for example by laser additive manufacturing, the feed compound particles bond to one another in a predetermined manner to produce a first molded part layer bonded to the first green part via a common interface. At least one additional layer of feed compound particles is then selectively densified on the first molded part layer to bond the feed compound particles to one another in a predetermined manner to produce at least one additional molded part layer bonded to the first molded part layer. The first molded part layer and the additional molded part layer form a unitary part with the first green part. The unitary part can then be removed from the build chamber and the unbonded particulate feed compound removed.
[0190] Preferably, the first green part has a DSC melting peak temperature T P The green part is preheated to a temperature close to 1000 K. This is to promote better bonding between the first green part and the second portion of the base compound.
[0191] In each step, the binder component (b) disperses among the sinterable non-organic particles (a) and holds them together after solidification. After the green part has been produced, it is removed from the unfused layer or mold.
[0192] According to one embodiment, partial removal of the temporary organic binder can be achieved by one or more of the following steps: - the first thermoplastic and / or wax-based material (bi) has a lower solvent solubility than the second thermoplastic and / or wax-based material (b-ii), and partial debinding is carried out by solvent treatment in a solvent treatment step; - the first thermoplastic material and / or wax-based material (bi) has a different thermal decomposition property and / or a different reactant decomposition property than the second thermoplastic material and / or wax-based material (b-ii), and the partial debinding is carried out by a thermal treatment in a thermal treatment step and / or a chemical treatment in a chemical treatment step; - the first thermoplastic and / or wax-based material (bi) has a different vapour pressure at a certain temperature than the second thermoplastic and / or wax-based material (b-ii), and partial debinding is carried out by heat treatment in a heat treatment step.
[0193] Among the processes for partially removing the binder, a solvent treatment process is preferred.
[0194] By using a first thermoplastic material and / or wax-based material (bi) having a different solvent solubility and / or a different thermal decomposition and / or a different reactant decomposition and / or a different volatility compared to the second thermoplastic material and / or wax-based material (b-ii), one or more binder components can be selectively removed during the debinding step. Preferably, the second thermoplastic material and / or wax-based material (b-ii) is selectively removed, while the first thermoplastic material and / or wax-based material (bi) is not removed. The part obtained after the debinding step is called a brown part. The brown part comprises sinterable non-organic particles (a) bound to each other by the first thermoplastic material and / or wax-based material (bi) and optionally remaining second thermoplastic material and / or wax-based material (b-ii).
[0195] The remaining binder components retained in the brown part provide a stable brown part that has sufficient strength for handling and transportation during the debinding and sintering steps.
[0196] In the solvent treatment step, the green part is immersed in a suitable solvent. Suitably, the solvent is selected such that the first thermoplastic and / or wax-based material (bi) is less soluble in the solvent than the second thermoplastic and / or wax-based material (b-ii) or, preferably, the first thermoplastic and / or wax-based material (bi) is essentially insoluble in the solvent and the second thermoplastic and / or wax-based material (b-ii) is soluble in the solvent. Suitable solvents are selected from alcohols such as ethanol or propanol; aromatic compounds such as benzene, toluene or xylene; esters such as ethyl acetate; ethers such as diethyl ether or tetrahydrofuran; ketones such as acetone; alkanes such as hexane or heptane; halogenated hydrocarbons such as n-propyl bromide, trichloroethylene, perchloroethylene, n-methylpyrrolidine; water; gases in a supercritical state; and mixtures thereof. During the solvent treatment step, the solvent is heated to a temperature T preferably in the range of 20 to 100°C, preferably 25 to 80°C, more preferably 30 to 60°C. L is kept constant.
[0197] In the chemical treatment step, the green part to be debound is treated in a reactive gas atmosphere. Preferably, the green part is placed in a reactive gas atmosphere, so that the reactive gas penetrates the pores of the green part containing the binder component. The binder component (b-ii) is degraded / decomposed by reaction with the reactive gas, and after removing the binder component (b-ii), a debound green part (brown part) is obtained. Such a reactive gas atmosphere may contain a gas, preferably nitric acid. Preferably, the chemical treatment step is carried out at an elevated temperature level. For example, the temperature in the chemical treatment step may be in the range of 40-150°C, preferably 60-140°C, more preferably 80-130°C.
[0198] Partial removal of the binder component (b-ii) results in the porous structure of the brown part: the sinterable non-organic particles (a) are held together by the first thermoplastic and / or wax-based material (bi).
[0199] Sintering process
[0200] In one embodiment, the method further comprises sintering the brown part to obtain a sintered component.
[0201] For this purpose, the brown part is preferably subjected to a sintering step after the debinding step, during which the first thermoplastic and / or wax-based material (bi) is removed and the debinding part (brown part) is sintered to obtain a sintered part. Usually, further removal of the binder and sintering of the brown part leads to shrinkage.
[0202] Suitably, the residual binder is removed at a first temperature T1 in the range of 100-750°C, preferably 150-700°C, more preferably 200-650°C, most preferably 300-600°C. A suitable temperature T1 may also depend on the atmosphere. Preferably, the first temperature T1 is selected as a function of the residual binder components, for example the first thermoplastic material and / or the wax-based material (bi). The removal of the first thermoplastic material and / or the wax-based material (bi) at temperature T1 is carried out for a time Δt1 that depends on the part geometry and is in particular proportional to the square of the wall thickness of the part to be manufactured. Preferably, the time Δt1 is selected such that at least 95%, preferably at least 99%, more preferably at least 99.9% and most preferably 100% of the binder components (bi) and (b-ii) are removed. The binder that is not removed is not available as a polymeric binder in the part but diffuses, for example as carbon, into the metal part, increasing the carbon content in the metal part. The thermal debinding may be carried out at multiple temperatures T1, for example at temperatures T 1a The removal of the portion of the first thermoplastic material and / or wax-based material (bi) at 1aThe test is carried out for a period of time at temperature T 1b The removal of the remainder of the first thermoplastic material and / or wax-based material (bi) at t 1b This will be carried out for a period of time.
[0203] The sinterable non-organic particles (a) form partial sintering necks that hold the part together when the remaining binder components are removed. The microporous structure of the part allows for rapid and uniform thermal debinding.
[0204] Undesirable chemical reactions during thermal binder removal can be avoided by an inert gas atmosphere or a reducing atmosphere or a high vacuum. The inert gas atmosphere in particular comprises at least one noble gas, which can be suitably selected, for example, from nitrogen, helium and argon. The reducing atmosphere can comprise gases such as hydrogen, carbon dioxide and / or carbon monoxide.
[0205] Suitably, sintering is carried out at a second temperature T2 in the range of 600-2000°C, preferably 800-1800°C, more preferably 900-1500°C. In the production of ceramic and / or glass parts, the second temperature T2 is preferably in the range of 600-2400°C, more preferably 800-2200°C, most preferably 1100-2000°C. In any case, the sintering temperature T2 is below the melting temperature of the sinterable non-organic particles. Sintering at the second temperature T2 is carried out for a time Δt2 that depends on the shape of the part and the material to be sintered. Preferably, the time Δt2 is long enough that subsequent further sintering does not cause significant changes in the porosity of the part. Sintering can be carried out at several temperatures T2. For example, at temperatures T 2a The sintering process is carried out for a time Δt 2a At temperature T 2b Then, perform another sintering process for time Δt 2b This will be carried out for a period of time.
[0206] During this sintering process, the molded part shrinks without essentially affecting its shape. The powder particles fuse and the voids between them disappear. Thus, the density of the product increases during sintering and the product shrinks. Usually, depending on the material of the product and its subsequent application, the sintering process is completed when the product has reached a density of about 90-100% relative to the volume of the solids that make up the powder.
[0207] Preferably, after the sintering step, the part is completely free of binder, so that it forms a dense, monolithic structure.
[0208] The present invention will now be described in detail with reference to the accompanying drawings and examples. [Brief description of the drawings]
[0209] [Figure 1] FIG. 1 shows the second heating gradient of the DSC measurement of binder component 1-B to determine the melting peak temperature TP of 1-B. [Diagram 2] FIG. 2 shows the second heating gradient of the DSC measurement of binder component 3-B to determine the melting peak temperature TP of 3-B. [Diagram 3] FIG. 3 shows the second heating gradient of the DSC measurement of binder component 4-B to determine the melting peak temperature TP of 4-B. [Figure 4] FIG. 4 shows the storage modulus G′ curve and loss modulus G″ curve of dynamic viscoelasticity measurement of binder component 1-B during heating to determine the crossover temperature Tcross of 1-B. [Diagram 5] FIG. 5 shows the storage modulus G′ curve and loss modulus G″ curve of dynamic viscoelasticity measurement of binder component 3-B during heating to determine the crossover temperature Tcross of 3-B. [Figure 6] Figure 6 shows the storage modulus G' and loss modulus G'' curves of dynamic viscoelastic measurements of binder component 4-B to determine the crossover temperature Tcross of 4-B. Figure 6 was recorded during cooling, since high values of Tcross were recorded during cooling. [Figure 7] FIG. 7 shows cylindrical test pieces (green parts) 1-F (FIG. 7A), 2-F (FIG. 7B), 3-F (FIG. 7C), and 4-F (FIG. 7D) obtained from the raw compound according to Table 2. [Figure 8] Figure 8 shows the front and back views of the test specimens (green parts) obtained by the molding process using raw compounds 1-F (Figure 8A), 2-F (Figure 8B), 3-F (Figure 8C), and 5-F (Figure 8D). [Figure 9] FIG. 9 shows the side and top views of a notched specimen obtained from the raw compound according to 1-F of Table 2. [Figure 10] FIG. 10 shows the side and top views of a notched specimen obtained from the raw compound according to Table 2, 2-F. [Figure 11] FIG. 11 shows the side and top views of a notched specimen obtained from the raw compound according to 3-F of Table 2. [Figure 12] FIG. 12 shows a rectangular first green part (FIG. 12A) 3D printed in a silicone mold and a one-piece part (FIG. 12B) produced by overcasting the rectangular first green part with molten feedstock compound. EXAMPLES
[0210] Working Example method Dynamic Mechanical Analysis Determination of storage and loss moduli
[0211] Dynamic viscoelastic measurements to determine the storage and loss moduli were carried out according to DIN 53019-4:2016-10 using a NETZSCH Kinexus Pro+ instrument equipped with a Peltier temperature-controlled measurement system. The measurements were carried out using a plate-plate geometry with a diameter of 40 mm and a frequency of 1 Hz in vibration mode. The measurement gap was 0.15 mm. To carry out the measurements, the geometry was heated to 110°C (160°C for Example 2-B in Table 3a and 140°C for Example 3-B in Table 3a) and the sample was placed on the hot lower plate. It was first cooled from 110°C (140°C, 160°C) to 60°C and then heated to 110°C (140°C, 160°C). The cooling and heating rates were each 1 K / min. For the cooling gradient, the measurements were started in deformation-controlled mode with a constant deformation γ=0.1%. After the trigger point was reached, the measurements were switched to the shear stress control mode with constant shear stress (σ = 100 Pa for binder and σ = 700 Pa for raw compound). For the heating gradient, the measurements were started in the shear stress control mode with constant shear stress σ = 300 Pa. After the trigger point was reached, the measurements were switched to the deformation control mode with constant deformation γ = 0.1%. For the heating gradient, the trigger points were deformation γ = 0.1%, except for binder 4-B, where the trigger point was 75 °C.
[0212] Viscosity measurements of binders and raw materials Dynamic viscoelastic measurements to determine the viscosity were carried out using a NETZSCH Kinexus Pro+ instrument equipped with a Peltier temperature-controlled measuring system according to EN ISO 3219:1994. The measurements were carried out using a plate-plate geometry with a diameter of 40 mm. The measuring gap was 0.15 mm. The measurements were carried out isothermally at the following temperatures: cross +20K, 100℃, and 130℃. 0.01 to 100s -1Various shear rates were applied during the time and the viscosity at different shear rates was measured. The measurements were carried out in the range of steady flow. Steady state is an indication of time-independent flow. Purely viscous flow leads to a steady state of 1. Viscosity values measured outside of time-independent flow are not reliable. Steady state values below 0.90 or above 1.10, preferably below 0.95 or above 1.05, more preferably below 0.97 or above 1.03 are assumed to be no longer fully reliable. In case of doubt, it is necessary to repeat the measurement or to select another suitable measurement setup, which is known per se, for example a different plate diameter, plate-cone geometry or concentric cylinder geometry.
[0213] DSC measurement DSC measurements were carried out using a NETZSCH DSC 214 Polymer instrument. Samples were prepared in aluminum Concavus pans (crucibles) with perforated lids from NETZSCH. For this purpose, the samples were heated with a first heating gradient from -20°C to 160°C (180°C for examples 2-B and 3-B in table 3a), then cooled to -20°C and finally heated again with a second heating gradient from -20°C to 160°C (180°C). The heating and cooling rates were each 1 K / min. Measurements were carried out with nitrogen quality 5.0 as purge gas and a gas flow rate of 40 mL / min.
[0214] Manufacturing Example According to Table 1, binder components 1-B to 5-B were produced. According to Table 2, raw material compounds 1-F to 5-F of binder components 1-B to 5-B were produced. Melting peak temperature T P , the intersection / "crossover" temperature T cross and the enthalpies of fusion are given in Tables 3a and 3b.
[0215] [Table 5]
[0216] [Table 6]
[0217] [Table 7]
[0218] [Table 8]
[0219] Green Parts Manufacturing Laser additive manufacturing Cylindrical test specimens were fabricated by laser additive manufacturing using a Formiga P110 (available from EOS GmbH). Raw materials Compounds 1-F to 5-F in Table 2 were used as starting materials.
[0220] For raw compound 1-F to 3-F, the laser power was 25 W, the powder bed surface temperature was 60 °C, and the laser speed was 4450 mm / s. The input energy changed as a result of changing the hatch spacing (0.13 mm vs. 0.07 mm): for the hatch spacing of 0.13 mm, the input energy was 42.3 mJ / mm 2 ;When the hatch spacing is 0.07 mm, the input energy is 78.5 mJ / mm 2 It was.
[0221] For raw compound 4-F, the laser speed was 3000 mm / s, the powder bed surface temperature was 60 °C, and the hatch spacing was 0.13 mm. The input energy changed as a result of changing the laser power (20 W vs. 25 W): for the laser power of 25 W, the input energy was 64.1 mJ / mm 2 ;When the laser output is 20W, the input energy is 51.3mJ / mm 2 It was.
[0222] Starting from raw compounds 1-F to 3-F in Table 2, notched specimens were fabricated by laser additive manufacturing using the aforementioned Formiga P110 (see "Cylindrical specimens"). In this specification, the term "notched specimen" refers to a rectangular solid containing one or more notches, which may have different widths. Such notched specimens are shown in side and top views in Figures 9 to 11.
[0223] In Fig. 9, raw compound 1-F was used as the starting material, and the laser power was 25 W, the laser speed was 4450 mm / s, and the hatch spacing was 0.13 mm, resulting in an input energy of 42.3 mJ / mm 2 It was.
[0224] In Fig. 10, raw compound 2-F was used as the starting material, and the laser power was 25 W, the laser speed was 4450 mm / s, and the hatch spacing was 0.07 mm, resulting in an input energy of 78.5 mJ / mm 2 It was.
[0225] In Fig. 11, raw compound 3-F was used as the starting material, and the laser power was 25 W, the laser speed was 4450 mm / s, and the hatch spacing was 0.07 mm, resulting in an input energy of 78.5 mJ / mm 2 It was.
[0226] The purpose of the production of such notched specimens was to obtain dense specimens, i.e. parts, with a high degree of representation of the desired part geometry and with little caking of the particulate raw compound, preferably with low laser energy input. The results are shown in Figures 9-11: 2 At a low laser energy input of 78.5 mJ / mm only the notched specimen shown in Figure 9 was dense, highly detailed, and had little caking. In contrast, the notched specimens in Figures 10 and 11 were irradiated with 78.5 mJ / mm 2 At this energy input, the density is low and / or the notch geometry is not suitable due to caking.
[0227] Molding process Further test specimens were prepared by the molding process using raw compounds 1-F, 2-F, 3-F and 5-F. To perform the molding process, a silicone mold with a rectangular cavity of 80 x 10 x 5 mm was prepared and preheated in an oven to a temperature of 60 ° C. The raw compounds to be investigated were melted at a temperature of 210 ° C (2-F, 3-F, 5-F) or 170 ° C (1-F) using a hot glue gun from "REKA Klebetechnik" and introduced into the rectangular cavity of the preheated mold with a pressure of 6 bar in order to press the raw compounds from the hot glue gun through an open nozzle with a diameter of 4 mm. After the molten raw compounds had solidified, the obtained test specimens were removed from the mold. To obtain test specimens with uniform surface properties, the protruding raw materials were polished off with sandpaper. A specimen made from Raw Compound 1-F is shown in Figure 8A; a specimen made from Raw Compound 2-F is shown in Figure 8B; a specimen made from Raw Compound 3-F is shown in Figure 8C; and a specimen made from Raw Compound 5-F is shown in Figure 8D. In each case, the front and back sides are shown.
[0228] Overcasting Process A rectangular first green part was made using the raw compound 1-F, which was overcast with the molten raw compound 1-F. The rectangular first green part was produced by 3D printing with the raw compound 1-F as described above and placed in a silicone mold with a rectangular parallelepiped cavity of 80 × 10 × 5 mm (see FIG. 12A). The mold containing the rectangular first green part was preheated in an oven to a temperature of 60 ° C. Then, the raw compound 1F was melted at a temperature of 170 ° C. using a hot glue gun from "REKA Klebetechnik" and introduced into the rectangular parallelepiped cavity of the preheated mold with a pressure of 6 bar in order to press the raw compound from the hot glue gun through an open nozzle with a diameter of 4 mm. After solidification, the obtained solid part was removed from the mold. A photograph of the solid part is shown in FIG. 12B; the sintered solid part is shown in FIG. 12C.
[0229] Manufacturing of sintered parts Tensile tests were carried out according to DIN EN ISO 22068 with tensile test specimens. The tensile test specimens were additively manufactured using the aforementioned Formiga P110 with the raw compound 1-F according to table 2 to obtain green parts. The green parts were then subjected to a solvent debinding and sintering step. For solvent debinding, the green parts of the raw compound 1-F were immersed in acetone for 6 h at a temperature of 40 °C and 16 h. Sintering was carried out with a heating and cooling rate of 5 K / min and cycles of holding times at 380 °C for 2 h, 600 °C for 1 h, 1100 °C for 30 min and a final sintering temperature of 1380 °C for 2 h. Five tensile tests were carried out according to DIN EN ISO 22068. The results are shown in Table 4.
[0230] [Table 9]
[0231] Rheometer measurements were performed using a Kinexus rheometer (available from NETZSCH) and viscosity measurements were performed according to EN ISO 3219:1994.
[0232] Tables 5 to 7 show the temperature at 100℃, 130℃ or T cross The viscosity values of binder components 1-B to 4-B and raw material compounds 1-F to 4-F measured at a temperature of +20K are shown.
[0233] [Table 10]
[0234] [Table 11]
[0235] [Table 12]
[0236] Additional Examples
[0237]
Table 13
[0238]
Table 14
[0239]
Table 15
[0240]
Table 16
[0241]
Table 17
[0242]
Table 18
[0243]
Table 19
[0244]
Table 20
[0245]
Table 21
Claims
1. 1. A binder component for a raw compound for use in a molding and sintering process, comprising: Based on the total volume of the binder component b), bi) 3 to 70 volume % of at least one thermoplastic material selected from polyesters, polyolefins, polyolefin waxes, polyamides, and polyacrylates; b-ii) 30 to 97 volume % of at least one wax-based material selected from polar waxes; Including; The thermoplastic material and the wax-based material have different solubilities in a solvent; the thermoplastic material is less soluble than the wax-based material; T cross , T P is higher by not more than 60K, preferably not more than 50K, more preferably not more than 45K, most preferably not more than 40K, particularly not more than 35K, compared to T P is the DSC melting peak temperature of binder component b), T cross is the temperature at the intersection of the storage modulus G' curve and the loss modulus G'' curve in the dynamic viscoelasticity measurement of the binder component b); Binder component.
2. T init and [T P +25K] is at least 94%, preferably at least 95%, more preferably at least 96%, most preferably at least 97%, particularly at least 98%, and particularly at least 99% (wherein T init is the incipient melting temperature), the binder component of claim 1 .
3. T P is in the range of less than 180°C, preferably from 10°C to 180°C, more preferably from 20°C to 160°C, most preferably from 30°C to 140°C, particularly from 35°C to 120°C, in particular from 40°C to 100°C, in particular from 45°C to 90°C, in particular from 50°C to 85°C.
4. Temperature of 130° C. and 1 s -1 3. A binder component according to claim 1 or 2, which exhibits a viscosity, measured at a shear rate of less than 6 Pa.s, preferably less than 5 Pa.s, more preferably less than 4 Pa.s, most preferably less than 3 Pa.s, in particular less than 2 Pa.s, especially less than 1 Pa.s, in particular less than 700 mPa.s, in particular less than 400 mPa.s, in particular less than 200 mPa.s.
5. Temperature of 110° C. and 1s -1 3. A binder component according to claim 1 or 2, which exhibits a viscosity, measured at a shear rate of less than 8 Pa.s, preferably less than 6 Pa.s, more preferably less than 5 Pa.s, most preferably less than 4 Pa.s, in particular less than 3 Pa.s, in particular less than 2 Pa.s, in particular less than 1 Pa.s, in particular less than 600 mPa.s, in particular less than 300 mPa.s.
6. Temperature of 100° C. and 1 s -1 3. A binder component according to claim 1 or 2, which exhibits a viscosity, measured at a shear rate of less than 10 Pa.s, preferably less than 8 Pa.s, more preferably less than 6 Pa.s, most preferably less than 5 Pa.s, particularly less than 4 Pa.s, in particular less than 3 Pa.s, in particular less than 2 Pa.s, in particular less than 1 Pa.s, in particular less than 500 mPa.s.
7. The amount of the thermoplastic material b-i) is in the range of about 5 to 60 vol.-%, preferably 7 to 50 vol.-%, more preferably 10 to 40 vol.-%, most preferably 12 to 35 vol.-%, in particular 15 to 30 vol.-%, based on the total volume of the binder component b), and / or 3. A binder component according to claim 1 or 2, wherein the amount of the wax-based material b-ii) is in the range of about 40-95 vol.-%, preferably 50-93 vol.-%, more preferably 60-90 vol.-%, most preferably 65-88 vol.-%, in particular 70-85 vol.-%, based on the total volume of binder component b).
8. 3. The binder component according to claim 1 or 2, wherein b-i) is selected from polycaprolactone, polylactide, polyglycolide, poly(hydroxyalkanoates), phthalate esters, polycarbonates, copolyesters, polyethylene, polypropylene, polyolefin copolymers, polyolefin copolymers with non-olefin monomers, modified polyolefins, homopolymers of propylene or higher 1-olefins, copolymers of propylene and ethylene or higher 1-olefins or copolymers thereof with each other, polyamide 12, copolyamides, polymethyl methacrylate.
9. 3. The binder component of claim 1 or 2, wherein b-ii) is selected from polyolefin waxes, ester waxes, amide waxes, higher organic acids, higher or polyhydric alcohols, polyethylene glycols and mixtures thereof.
10. 10. The binder component of claim 9, wherein b-ii) is selected from aromatic esters and aromatic sulfonamides.
11. The binder component according to claim 1 or 2, comprising a combination of the thermoplastic material bi) selected from the following table and the wax-based material b-ii). 【Table 1】 【Table 2】 【Table 3】 【Table 4】
12. 1. A particulate feed compound for use in a compacting and sintering process, comprising: a) sinterable non-organic particles dispersed throughout the particulate raw compound, at least 80% of the particles having a maximum particle size A in the range of 100 nm to 400 μm; max non-organic particles having a particle size distribution having b) A binder component according to claim 1 or 2.
13. 13. The particulate feed compound of claim 12, wherein the sinterable non-organic particles are selected from the following: a-i) metal particles selected from iron, stainless steel, steel, copper, bronze, aluminum, tungsten, molybdenum, silver, gold, platinum, titanium, nickel, cobalt, chromium, zinc, niobium, tantalum, yttrium, silicon, magnesium, calcium, and combinations thereof, wherein at least 85%, preferably at least 90%, more preferably at least 95%, and most preferably at least 99% of the particles have a maximum particle size A in the range of 500 nm to 400 μm, preferably 1 μm to 150 μm, more preferably 3 μm to 50 μm, and most preferably 5 μm to 25 μm. max Metal particles having a particle size distribution having a-ii) Ceramic particles selected from oxides such as aluminum oxide, silicon oxide, zirconium oxide, titanium oxide, magnesium oxide, yttrium oxide, etc.; carbides such as silicon carbide, tungsten carbide, etc.; nitrides such as boron nitride, silicon nitride, aluminum nitride, etc.; silicates such as steatite, cordierite, mullite, etc.; and combinations thereof, wherein at least 85%, preferably at least 90%, more preferably at least 95%, and most preferably at least 99% of the particles have a maximum particle size A in the range of 200 nm to 25 μm, preferably 300 nm to 10 μm, more preferably 400 nm to 7 μm, and most preferably 500 nm to 3 μm. max Ceramic particles having a particle size distribution having a-iii) glass particles selected from non-oxide glasses such as halide glasses, chalcogenide glasses; oxide glasses such as phosphate glasses, borate glasses, silicate glasses, e.g., aluminosilicate glasses, lead silicate glasses, boron silicate glasses, soda-lime silicate glasses, quartz glasses, alkali silicate glasses; and combinations thereof, wherein at least 85%, preferably at least 90%, more preferably at least 95%, and most preferably at least 99% of the particles have a maximum particle size A in the range of 200 nm to 25 μm, preferably 300 nm to 10 μm, more preferably 400 nm to 7 μm, and most preferably 500 nm to 3 μm. max glass particles having a particle size distribution having a-iv) Combinations of more than one of ai) to a-iii) sinterable non-organic particles such as hard metals or metal matrix composites.
14. Sinterable non-organic particles (a) are about 0.70 to 0.99 mm diameter on a volume basis. r , preferably about 0.75 to 0.98·φ r , more preferably about 0.80 to 0.96·φ r , and most preferably about 0.82 to 0.95·φ r , especially about 0.84 to 0.94 mm r , especially about 0.86 to 0.93 mm r The amount of (where φ r 13. The particulate feed compound of claim 12, comprising:
15. the amount of sinterable non-organic particles (a) is in the range of about 20-90 vol%, preferably 30-80 vol%, more preferably 40-75 vol%, most preferably 45-70 vol%, especially 50-65 vol%, and 13. The particulate feed compound of claim 12, wherein the amount of binder component (b) is in the range of about 10 to 80 vol%, preferably 20 to 70 vol%, more preferably 25 to 60 vol%, most preferably 30 to 55 vol%, especially 35 to 50 vol%.
16. Temperature: 130°C, shear rate: 1s -1 The particulate raw material compound according to claim 12, having a viscosity measured at 1000000000000000000000000000000000000, more preferably less than 600 Pa·s, preferably less than 400 Pa·s, more preferably less than 350 Pa·s, most preferably less than 250 Pa·s, particularly less than 150 Pa·s, in particular less than 50 Pa·s, in particular less than 10 Pa·s.
17. Temperature: 110°C, shear rate: 1s -1 The particulate raw material compound according to claim 12, having a viscosity measured at 1000 g / mol / L of less than 800 Pa·s, preferably less than 550 Pa·s, more preferably less than 450 Pa·s, most preferably less than 350 Pa·s, particularly less than 200 Pa·s, in particular less than 100 Pa·s, in particular less than 60 Pa·s.
18. Temperature: 100°C, shear rate: 1s -1 The particulate raw material compound according to claim 12, having a viscosity measured at 1000 Pa·s, preferably less than 850 Pa·s, more preferably less than 700 Pa·s, most preferably less than 550 Pa·s, particularly less than 400 Pa·s, in particular less than 250 Pa·s, in particular less than 100 Pa·s.
19. A method comprising the steps of: - fusing a plurality of the particulate raw material compounds according to claim 12 to obtain a green part; - partially debinding the green part by selectively removing said wax-based material (b-ii) to obtain a brown part comprising sinterable non-organic powder particles (a) bound together by said thermoplastic material (bi); and - Sintering the brown part to obtain a sintered part.
20. 20. The method of claim 19, wherein the method is selected from additive manufacturing methods such as laser additive manufacturing or extrusion additive manufacturing; injection molding methods such as medium pressure injection molding or low pressure injection molding; pressing methods; and casting methods.
21. A green part obtained by fusing a plurality of particulate raw material compounds described in claim 12.